Toner and method for producing toner
By using core-shell structure and specific testing methods in the toner to optimize its energy storage elastic modulus and yield point, the stability and fixing performance problems of toner at high temperature and high humidity are solved, and the harsh environment is achieved Efficient image printing.
Patent Information
- Application Number
- CN202010396831.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-13
- Filing Date
- 2020-05-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-05-12
AI Technical Summary
The existing toners are prone to soften in high temperature environments, resulting in rupture and crushing, degradation of fluidity and charged properties, and poor fixing performance in high humidity environments, making it prone to back-end staining.
Using toner with a core-shell structure, the energy storage elastic modulus and yield point of the toner are optimized through powder dynamic viscoelastic measurement method and nano-indentation method, and its stability in high temperature and high humidity are improved. Durability ensures low temperature fixability and storage stability.
Suppress the cracking and crushing of toner in a high temperature environment, prevent back-end staining, maintain image quality, and improve storage stability and fixing performance.
Smart Images

Figure BDA0002487896460000161 
Figure BDA0002487896460000411 
Figure BDA0002487896460000421
Abstract
Description
Technical Field
[0001] The present disclosure relates to a toner suitable for a recording method using an electrophotographic method, an electrostatic recording method, and a toner jet recording method, and a method for producing the toner. Background Art
[0002] Electrophotographic image forming devices are required to have higher speed, longer life, and energy saving, and in order to cope with these requirements, further improvements in various performance characteristics are also required for toners. In particular, from the viewpoint of faster speed and energy saving, further improvements in the low temperature fixability of toners are required. It is also important that toners do not change in various transport environments and use environments. In particular, transport and storage under high temperature and high humidity are likely to affect toners, and it is desired that toners have high heat-resistant storage performance.
[0003] In order to achieve low-temperature fixability, it is necessary to create a state in which the binder resin is plasticized and easily fused during fixing. Generally, the fixing performance can be improved by using a toner having a binder resin designed to be soft. However, the problem with this method is that the resin is not only soft during fixing, but also has problems with heat-resistant storage stability and durability.
[0004] In order to solve this problem, for example, a toner having a core-shell structure is proposed, thereby providing a toner having both low-temperature fixability and durability.
[0005] Japanese Patent Publication No. 2009-156902 discloses a toner having a core-shell structure using a first binder resin and a second binder resin, thereby providing a toner particle whose inner side is soft and outer side is hard and which is satisfactory in strength against mechanical stress and fixing performance.
[0006] In addition, from the viewpoint of extending the service life, it is necessary to improve the durability of the toner surface. The toner in the toner box is subjected to strong stresses, such as due to friction at various positions. As the number of developing operations increases, the number of times the toner is subjected to stress increases, which causes the toner to break or break or the embedding of external additives. Since the toner's break and break and the embedding of external additives may reduce the fluidity or charging performance of the toner, it is necessary to harden the surface of the toner particles.
[0007] Japanese Patent Publication No. 2008-164771 proposes using A toner manufactured so that the elastic modulus of the toner can be specified and a high-quality image can be obtained stably for a long time. Summary of the invention
[0008] However, even with the toner described in Japanese Patent Publication No. 2009-156902, in a high-speed electrophotographic image forming apparatus, there is room for improvement in durability.
[0009] Furthermore, in the case of the toner described in Japanese Patent Literature Publication No. 2008-164771, satisfactory results in terms of fixing performance, density unevenness, fogging, etc. are obtained, but there is room for improvement in the mechanical strength of the toner.
[0010] The present disclosure provides a toner having excellent low-temperature fixability and excellent storage stability and durability, and a method for producing the toner.
[0011] The toner of the present disclosure is a toner comprising toner particles including a binder resin, wherein
[0012] Toner is to make
[0013] (1) When the powder dynamic viscoelasticity measurement method is used, the measurement start temperature is set to 25° C., and the temperature increase rate is set to 20° C. / min, on a curve of storage elastic modulus E' in which temperature (° C.) is plotted as the abscissa and storage elastic modulus E' (Pa) is plotted as the ordinate, the temperature at which the storage elastic modulus E' at the start of measurement decreases by 50% is 60° C. to 90° C., and
[0014] (2) The load at the yield point of a displacement-load curve determined by a nanoindentation method, in which the load (mN) is plotted on the ordinate and the displacement (μm) is plotted on the abscissa, is 0.80 mN or more.
[0015] The method for producing a toner disclosed herein is a method for producing a toner including toner particles including a binder resin, the method comprising:
[0016] Step (I): dispersing a polymerizable monomer composition including a polymerizable monomer capable of forming a binder resin in an aqueous medium and forming particles of the polymerizable monomer composition in the aqueous medium, and
[0017] Step (II): polymerizing the polymerizable monomers included in the particles of the polymerizable monomer composition, wherein
[0018] Toner is to make
[0019] (1) When the powder dynamic viscoelasticity measurement method is used, the measurement start temperature is set to 25° C., and the temperature increase rate is set to 20° C. / min, on a curve of storage elastic modulus E' in which temperature (° C.) is plotted as the abscissa and storage elastic modulus E' (Pa) is plotted as the ordinate, the temperature at which the storage elastic modulus E' at the start of measurement decreases by 50% is 60° C. to 90° C., and
[0020] (2) The load at the yield point of a displacement-load curve determined by a nanoindentation method, in which the load (mN) is plotted on the ordinate and the displacement (μm) is plotted on the abscissa, is 0.80 mN or more.
[0021] According to the present disclosure, a toner having excellent low-temperature fixing ability and excellent storage stability and durability, and a method for producing the toner can be provided.
[0022] Further features of the present invention will become apparent from the following description of exemplary embodiments. DETAILED DESCRIPTION
[0023] In the present disclosure, unless otherwise specified, the descriptions "from XX to YY" and "XX to YY" indicating a numerical range refer to a numerical range including an upper limit and a lower limit as endpoints. In addition, the description "A and / or B" is a concept including the case of A, the case of B, and the case of both A and B.
[0024] The present inventors have extensively studied on a toner that can achieve low-temperature fixability, as well as storage stability and durability.
[0025] Based on the results obtained by the present inventors, it has been found that the durability of the toner becomes more disadvantageous in a high temperature environment. The reason for this is that at a higher ambient temperature, the toner may soften and is more likely to crack and break during durable output. As a result, the fluidity of the toner decreases, the charging performance decreases, and fogging occurs.
[0026] When inorganic fine particles such as silica fine particles are present on the surface of the toner particles, cracking and breaking are more likely to occur. This is because when the toner softens under a high temperature environment, the inorganic fine particles on the surface of the toner particles are easily embedded in the toner. During long-term use in the cartridge, embedding of inorganic fine particles inside the toner is more likely to occur.
[0027] That is, when the toner particles are subjected to mechanical stress, for example, when inorganic fine particles are present on the surface of the toner particles, the contact area between the toner particles is reduced, and the mechanical stress can be dispersed. However, the inorganic fine particles on the surface of the toner particles may move from the surface of the toner particles to the inside of the toner particles due to long-term use in the cartridge. As a result, the number of inorganic fine particles on the surface of the toner particles for dispersing the mechanical stress is substantially reduced, so the toner is easily broken and fragmented, and the charging performance is reduced.
[0028] Meanwhile, when the hardness of the toner is increased in order to suppress cracking and breaking of the toner, melting and spreading of the toner at the time of fixing tend to be insufficient, and trailing edge offset, which serves as an index of low-temperature fixability described later, tends to occur.
[0029] Generally, film fixing is performed under a small heat capacity and a light pressure, so that sufficient heat may not be transferred to the toner. In recent years, printers are often used in various environments around the world. In particular, in a high humidity environment, the heat of the fixing film is taken away by moisture, and the amount of heat given to the toner may be further reduced.
[0030] When the temperature of the fixing film is too low, the toner is not sufficiently melted, a temperature gradient is generated inside the toner layer, so that the interface temperature between the lowermost surface of the toner layer and the paper surface does not become a temperature sufficient to melt the toner, and the toner layer breaks. The resulting problem is cold offset in which the toner adheres to the fixing film when passing through the fixing nip, passes a circle while adhering to the film, and is fixed on the paper.
[0031] When the amount of toner carried on paper increases during printing of an image with a high printing percentage such as a full-surface solid black image, the amount of heat applied to each toner particle decreases, and the cold offset phenomenon is particularly likely to occur at the rear end portion (this is particularly called rear end offset). This is because the heat of the fixing film is taken away by the toner placed on the front half of the paper, making it more difficult for the toner transferred to the rear end portion of the paper to melt.
[0032] Studies conducted by the present inventors have revealed that the toner on paper having a full-surface solid black image fixed at the lowest temperature at which rear end offset does not occur is fixed in a state where about 50% of the lumps remain intact while being melted and connected, and the toner particles are not sufficiently bonded. That is, it was found that the rear end offset is a phenomenon caused by insufficient adhesion between the particles of the toner. Therefore, it was found that, in order to suppress the rear end offset, it is important to melt the toner at a lower temperature, thereby achieving a viscous state, and improving the adhesion between the particles of the toner.
[0033] However, when the melt viscosity of the toner is simply reduced to solve the problem, brittle fracture of the toner itself may occur when the process speed is increased or the number of development operations is increased.
[0034] As described above, there is a trade-off relationship between suppressing toner breakage and crushing and suppressing trailing end offset, and it is difficult to achieve both of them when considering increasing the speed and extending the life of the printer under a severe environment.
[0035] With the toner of the present disclosure, cracking and breaking of the toner can be suppressed at a high level even under a high-temperature environment, and at the same time, an image with no rear end offset can be obtained even under a high-humidity environment.
[0036] That is, the toner of the present disclosure is a toner comprising toner particles including a binder resin, wherein
[0037] Toner is to make
[0038] (1) When the powder dynamic viscoelasticity measurement method is used, the measurement start temperature is set to 25° C., and the temperature increase rate is set to 20° C. / min, on a curve of storage elastic modulus E' (Pa) in which temperature (° C.) is plotted as the abscissa and storage elastic modulus E' is plotted as the ordinate, the temperature at which the storage elastic modulus E' at the start of measurement decreases by 50% is 60° C. to 90° C., and
[0039] (2) The load at the yield point of a displacement-load curve determined by a nanoindentation method, in which the load (mN) is plotted on the ordinate and the displacement (μm) is plotted on the abscissa, is 0.80 mN or more.
[0040] The inventors first studied a toner that can maintain strength even in a high temperature environment. In the present disclosure, nanoindentation is used as an indicator of toner strength. Nanoindentation is an evaluation method that pushes a diamond indenter into a sample placed on a workbench, measures the load (indentation strength) and displacement (indentation depth), and analyzes mechanical properties from the obtained load-displacement curve.
[0041] As a method for evaluating the mechanical properties of toner, a micro compression tester is generally used. In the micro compression test, the indenter is larger than the size of the toner, and the test is suitable for evaluating the macroscopic mechanical properties of the toner.
[0042] However, the cracking and breaking of the toner, which is the focus of the present disclosure, especially the cracking, is affected by the micromechanical properties of the toner, so the characteristic evaluation in a smaller area is required. In the measurement by the nanoindentation method, the indenter has a triangular pyramid shape, and the tip of the indenter is much smaller than the size of the toner. Therefore, this method is suitable for evaluating the micromechanical properties of the toner.
[0043] The present inventors conducted intensive studies and found that it is important to control the load at the yield point obtained by measurement using a nanoindentation method, which is a micromechanical characteristic of the toner, within a specific range.
[0044] That is, in the toner of the present disclosure, the load corresponding to the yield point on the displacement-load curve when the load (mN) is plotted as the ordinate and the displacement amount (μm) is plotted as the abscissa determined by the nanoindentation method is 0.80 mN or more.
[0045] In measurement using the nanoindentation method, the indenter is pushed into the sample while continuously changing an extremely small load on the toner, the displacement at this time is measured, and a displacement-load curve is created when the load (mN) is plotted as the ordinate and the displacement amount (μm) is plotted as the abscissa.
[0046] It is considered that under a load at the maximum value of a differential curve obtained by differentiating the load-displacement curve with respect to the load, that is, under a load at which the slope on the load-displacement curve is the largest, the toner undergoes a large deformation, that is, a phenomenon corresponding to rupture occurs. Therefore, in the present disclosure, the load at which the slope on the load-displacement curve is the largest is taken as the load at which the toner ruptures, and this load is defined as the "yield point". In other words, a high load at which the slope is the largest indicates that a high load is required for the toner to rupture, indicating that the toner is more difficult to rupture.
[0047] It was found that by controlling the load corresponding to the yield point to 0.80 mN or more, the effect of suppressing toner cracking and crushing can be obtained, especially in a system with high speed and long life, and the storage stability under high temperature environment is significantly improved.
[0048] The load corresponding to the yield point is preferably 0.85 mN or more, or more preferably 0.87 mN or more.
[0049] The upper limit of the load corresponding to the yield point is not particularly limited, because the higher the value, the higher the strength of the toner, and the easier it is to suppress the breakage of the toner. However, when the upper limit is higher than 1.80 mN, rear end deterioration tends to occur. Therefore, the load corresponding to the yield point is preferably 1.80 mN or less, more preferably 1.50 mN or less.
[0050] The numerical ranges of the yield point can be arbitrarily combined. The numerical range of the yield point can be controlled by adjusting the types and amounts of the binder resin, the crystalline material D, and the crystalline material E, and the area ratio A1 described later.
[0051] By increasing the load corresponding to the yield point as described above, the cracking and breaking of the colorant can be suppressed. In the present disclosure, in combination with suppressing the cracking and breaking of the colorant, by designing the colorant so that the inside is easily melted, the occurrence of rear end stain, which is an indicator of low temperature fixability, can be significantly suppressed even in a high humidity environment.
[0052] Specifically, the present inventors studied the viscoelastic properties of toner in order to design a toner that can suppress rear end offset under a high-humidity environment.
[0053] Powder dynamic viscoelasticity measurement (hereinafter, also referred to as DMA) is a method capable of measuring the viscoelastic properties of a toner as a powder. As a result of research conducted by the present inventors, it was found that when the powder dynamic viscoelasticity measurement method is used, the measurement start temperature is set to 25°C, and the temperature increase rate is set to 20°C / min, on a curve of the storage elastic modulus E' in which the temperature (°C) is plotted as the abscissa and the storage elastic modulus E' (Pa) is plotted as the ordinate, the temperature at which the storage elastic modulus E' at the start of the measurement decreases by 50% can be used to verify the viscoelasticity of the toner at the time of fixing.
[0054] In conventional viscoelasticity measurement, the measurement is usually performed after the toner is molded by heat or pressure, so the measurement result can be said to represent the averaged viscoelastic properties of the entire toner, and it is believed that it cannot represent the properties of the toner when it is fixed. At the same time, it is believed that since the powder dynamic viscoelasticity measurement can measure the toner in the powder state, the result can satisfactorily reflect the state of the toner when it is fixed.
[0055] As described above, the toner on the paper having the full-surface solid black image fixed at the lowest temperature at which the rear end stain does not occur is fixed in a state of being melted and connected while 50% of the lumps remain, and the particles of the toner are not sufficiently bonded. As a result of further investigation, it was found that on the curve of the storage elastic modulus E' obtained by the dynamic viscoelasticity measurement of the powder, the temperature at which the storage elastic modulus E' at the start of the measurement decreases by 50% is the temperature at which the elastic modulus of the toner decreases and the toner begins to acquire viscosity. It was found that at this time, adhesion occurs between the particles of the toner, which is well correlated with the lowest temperature at which the rear end stain does not occur.
[0056] The temperature at which the storage elastic modulus E' at the start of the measurement decreases by 50% is 60°C to 90°C. Within this range, melting of the toner occurs at a lower temperature, and the occurrence of rear end stain is suppressed. When the temperature is lower than 60°C, the storage stability decreases, brittle fracture of the toner itself may occur, and fogging occurs after long-term use. Meanwhile, when the temperature is higher than 90°C, the toner does not melt at a lower temperature, and rear end stain occurs.
[0057] The temperature at which the storage elastic modulus E' at the start of measurement decreases by 50% is preferably 70°C to 84°C, and more preferably 74°C to 80°C.
[0058] The temperature at which the storage elastic modulus E' at the start of measurement decreases by 50% can be controlled by adjusting the kinds and amounts of the binder resin, the crystalline material D, and the crystalline material E, and the area ratio A1 described below.
[0059] The toner particles include a binder resin. The amount of the binder resin is preferably 45% by mass to 70% by mass, and more preferably 50% by mass to 65% by mass, based on the toner particles.
[0060] The binder resin is not particularly limited, and a known resin used for toner can be used. The binder resin preferably includes the resin B, more preferably includes the resin B in an amount of 50% by mass or more, and further preferably includes the resin B in an amount of 100% by mass.
[0061] Furthermore, the resin B is preferably a non-crystalline resin.
[0062] When the dipole interaction term of the Hansen solubility parameter of resin B is b (unit: MPa 1 / 2 ), b is preferably 1.0 to 3.5, and more preferably 1.2 to 1.5. b can be controlled by changing the kind of monomer constituting the resin B.
[0063] Here, the "dipole interaction term of the Hansen solubility parameter" refers to the polarization term δp (unit: MPa) that represents the energy from the dipole interaction among the three parameters constituting the Hansen solubility parameter. 1 / 2 ).
[0064] As the resin B, for example, a vinyl resin is used.
[0065] Monomers usable in the production of the vinyl resin, that is, polymerizable monomers capable of forming the vinyl resin can be exemplified by the following monomers. The following monomers can be used alone or in combination of two or more.
[0066] Aliphatic vinyl hydrocarbons: olefins, for example, ethylene, propylene, butene, isobutylene, pentene, heptene, diisobutylene, octene, dodecene, octadecene, and other α-olefins; alkadienes, for example, butadiene, isoprene, 1,4-pentadiene, 1,6-hexadiene, and 1,7-octadiene.
[0067] Alicyclic vinyl hydrocarbons: monocyclic or bicyclic olefins and alkadienes, for example, cyclohexene, cyclopentadiene, vinylcyclohexene, ethylidenebicycloheptene; terpenes, for example, pinene, limonene and indene.
[0068] Aromatic vinyl hydrocarbons: styrene and its hydrocarbon (alkyl, cycloalkyl, aralkyl and / or alkenyl) substituents, for example, α-methylstyrene, vinyltoluene, 2,4-dimethylstyrene, ethylstyrene, isopropylstyrene, butylstyrene, phenylstyrene, cyclohexylstyrene, benzylstyrene, crotylbenzene, divinylbenzene, divinyltoluene, divinylxylene, and trivinylbenzene; and vinylnaphthalene.
[0069] Carboxyl-containing vinyl monomers and metal salts thereof: unsaturated monocarboxylic acids, unsaturated dicarboxylic acids, anhydrides and monoalkyl (1 to 27 carbon atoms) esters thereof having 3 to 30 carbon atoms. For example, carboxyl-containing vinyl monomers of acrylic acid, methacrylic acid, maleic acid, maleic anhydride, monoalkyl esters of maleic acid, fumaric acid, monoalkyl esters of fumaric acid, crotonic acid, itaconic acid, monoalkyl esters of itaconic acid, glycol monoethers of itaconic acid, citraconic acid, monoalkyl esters of citraconic acid, and cinnamic acid.
[0070] Vinyl esters, for example, vinyl acetate, vinyl butyrate, vinyl propionate, vinyl butyrate, diallyl phthalate, diallyl adipate, isopropenyl acetate, vinyl methacrylate, methyl 4-vinylbenzoate, cyclohexyl methacrylate, benzyl methacrylate, phenyl acrylate, phenyl methacrylate, methoxyvinyl acetate, vinyl benzoate, α-ethoxyethyl acrylate, alkyl acrylates and alkyl methacrylates having an alkyl group (linear or branched) of 1 to 22 carbon atoms (methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, lauryl acrylate, lauryl methacrylate, myristyl acrylate, myristyl methacrylate, hexadecyl acrylate, hexadecyl methacrylate, stearyl acrylate, methyl acrylate
[0063] The present invention also includes the following: stearyl acrylate, eicosyl acrylate, eicosyl methacrylate, behenyl acrylate, behenyl methacrylate, etc.), dialkyl fumarate (dialkyl ester of fumaric acid, two alkyl groups are each independently a linear, branched or alicyclic group having 2 to 8 carbon atoms), polyallyloxyalkanes (diallyloxyethane, triallyloxyethane, tetraallyloxyethane, tetraallyloxypropane, tetraallyloxybutane, and tetramethylallyloxyethane), vinyl monomers having a polyalkylene glycol chain (polyethylene glycol (molecular weight 300) monoacrylate, polyethylene glycol (molecular weight 300) monomethacrylate, polypropylene glycol (molecular weight 500) monoacrylate, polypropylene glycol (molecular weight 500) monomethacrylate, methanol ethylene oxide (hereinafter ethylene oxide is abbreviated as EO) 10 mol adduct acrylate, methanol ethylene oxide 10 mol adduct methacrylate, lauryl alcohol EO 30 mol adduct acrylate, lauryl EO 30 mol adduct methacrylate), multiacrylates and multimethacrylates (polyacrylates and multimethacrylates of polyols: ethylene glycol diacrylate, ethylene glycol dimethacrylate, propylene glycol diacrylate, propylene glycol dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, polyethylene glycol diacrylate, and polyethylene glycol dimethacrylate).
[0071] Carboxyl group-containing vinyl esters: for example, carboxyl alkyl acrylates having an alkyl chain having 3 to 20 carbon atoms, and carboxyl alkyl methacrylates having an alkyl chain having 3 to 20 carbon atoms.
[0072] As a monomer usable in the production of the vinyl resin, that is, a polymerizable monomer capable of forming the vinyl resin, acrylonitrile and the like can be used in addition to the above monomers.
[0073] The toner particles preferably include a colorant. Examples of the colorant include pigments, dyes, magnetic bodies, etc. These may be used alone or in combination of two or more.
[0074] Examples of black pigments include carbon black such as furnace black, channel black, acetylene black, thermal black, lamp black, etc. These may be used alone or in combination of two or more.
[0075] Pigments or dyes can be used as colorants suitable for yellow. Examples of pigments include CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 17, 23, 62, 65, 73, 74, 81, 83, 93, 94, 95, 97, 98, 109, 110, 111, 117, 120, 127, 128, 129, 137, 138, 139, 147, 151, 154, 155, 167, 168, 173, 174, 176, 180, 181, 183 and 191, and CI Vat Yellow 1, 3 and 20. Examples of dyes include CI Solvent Yellow 19, 44, 77, 79, 81, 82, 93, 98, 103, 104, 112 and 162. These may be used alone or in combination of two or more.
[0076] A pigment or dye may be used as a colorant suitable for cyan. Examples of the pigment include CI Pigment Blue 1, 7, 15, 15; 1, 15; 2, 15; 3, 15; 4, 16, 17, 60, 62 and 66, CI Vat Blue 6, and CI Acid Blue 45. Examples of the dye include CI Solvent Blue 25, 36, 60, 70, 93 and 95. These may be used alone or in combination of two or more.
[0077] A pigment or dye may be used as a colorant suitable for magenta. Examples of the pigment include CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48, 48; 2, 48; 3, 48; 4, 49, 50, 51, 52, 53, 54, 55, 57, 57; 1, 58, 60, 63, 1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 144, 146, 150, 163, 166, 169, 177, 184, 185, 202, 206, 207, 209, 220, 221, 238 and 254, CI Pigment Violet 19, and CI Vat Red 1, 2, 10, 13, 15, 23, 29 and 35.
[0078] Examples of the dye for magenta include oil-soluble dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 52, 58, 63, 81, 82, 83, 84, 100, 109, 111, 121 and 122, CI Disperse Red 9, CI Solvent Violet 8, 13, 14, 21 and 27, and CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39 and 40, CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27 and 28. These may be used alone or in combination of two or more.
[0079] The toner particles preferably include a magnetic body as a colorant.
[0080] Examples of magnetic bodies include iron oxides such as magnetite, hematite, ferrite, etc.; metals such as iron, cobalt, and nickel; or alloys or mixtures of these metals with aluminum, copper, magnesium, tin, zinc, beryllium, calcium, manganese, selenium, titanium, tungsten, and vanadium.
[0081] The number average particle size of the primary particles of the magnetic substance is preferably 500 nm or less, more preferably 50 nm to 350 nm.
[0082] The number average particle size of the primary particles of the magnetic body present in the toner particles can be measured using a transmission electron microscope.
[0083] Specifically, after the toner to be observed is fully dispersed in the epoxy resin, the toner is cured for 2 days in an atmosphere at a temperature of 40°C to obtain a cured product. The cured product is used as a thin slice sample obtained by a microtome, and an image with a magnification of 10,000 to 40,000 times is taken with a transmission electron microscope (hereinafter also referred to as TEM), and the projected area of 100 primary particles of the magnetic body in the image is measured. The equivalent diameter of a circle equal to the projected area is defined as the particle size of the primary particles of the magnetic body, and the average value of 100 particles is defined as the number average particle size of the primary particles of the magnetic body.
[0084] The amount of the magnetic body is preferably 35.0 to 100.0 parts by mass, more preferably 45.0 to 90.0 parts by mass, and even more preferably 50.0 to 70.0 parts by mass, relative to 100.0 parts by mass of the binder resin or the polymerizable monomer capable of forming the binder resin.
[0085] When the amount of the magnetic body is within the above range, the magnetic attraction force with the magnetic roller in the developing sleeve becomes moderate. In addition, the hardness of the toner surface becomes moderate, and the load corresponding to the yield point can be easily adjusted within the above range.
[0086] The amount of the magnetic body in the toner can be measured using a thermal analyzer TGA Q5000IR manufactured by Perkin Elmer Corp. In the measurement, the magnetic toner is heated from normal temperature to 900° C. at a temperature increase rate of 25° C. / min under a nitrogen atmosphere, the mass loss from 100° C. to 750° C. is taken as the mass of the component after the magnetic body is excluded from the toner, and the remaining mass is taken as the mass of the magnetic body.
[0087] The magnetic body can be produced, for example, by the following method.
[0088] An alkali such as sodium hydroxide is added to an aqueous solution of ferrous salt in an amount equivalent to or greater than the iron component to prepare an aqueous solution containing ferrous hydroxide. Air is blown into the prepared aqueous solution while maintaining the pH value of the aqueous solution at 7 or greater, and an oxidation reaction of the ferrous hydroxide is performed while the aqueous solution is heated to 70° C. or greater to first generate seed crystals serving as nuclei of magnetic iron oxide.
[0089] Then, based on the amount of the alkali added before, the aqueous solution containing about 1 equivalent of ferrous sulfate is added to the slurry containing seed crystals. The pH of the mixed solution is maintained at 5 to 10, and the reaction of ferrous hydroxide is carried out while air is blown in, and magnetic iron oxide is grown around the seed crystals. At this time, the shape and magnetic properties of the magnetic body can be controlled by selecting any pH, reaction temperature and stirring conditions. Along with the oxidation reaction, the pH of the mixed solution moves to the acidic side, but the pH of the mixed solution is preferably more than 5. The magnetic body obtained in this way can be obtained by filtering, washing and drying the magnetic body by a conventional method.
[0090] The toner particles preferably contain a surface-treated magnetic body A having a magnetic body and a hydrophobizing agent containing an organic compound having a hydrophobic group on the surface of the magnetic body.
[0091] The surface-treated magnetic body A is obtained by surface treatment with a hydrophobizing agent containing an organic compound having a hydrophobic group.
[0092] The hydrophobic group may be, for example, a hydrocarbon group having 8 to 16 carbon atoms.
[0093] When the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is a (unit: MPa 1 / 2 ), a is preferably 1.40 to 2.10, more preferably 1.70 to 2.04, and even more preferably 1.80 to 2.00. The value of a can be controlled by changing the kind of the hydrophobizing treatment agent.
[0094] Examples of the organic compound having a hydrophobic group include silane compounds having a hydrocarbon group having a carbon number of 8 to 16. Examples of the silane compound include a silane coupling agent.
[0095] The silane coupling agent is more preferably an alkyltrialkoxysilane coupling agent represented by the following formula (I).
[0096] C p H 2p+1 -Si-(OC q H 2q+1 )3 (I)
[0097] In formula (I), p represents an integer of 8-16, and q represents an integer of 1-3.
[0098] When p in formula (I) is 8 or more, sufficient hydrophobicity can be imparted. It is preferable that p is 16 or less because the surface of the magnetic body can be uniformly treated and aggregation of the magnetic body can be suppressed.
[0099] By treating with a hydrophobizing agent by, for example, a treatment method described later, the hydrophobicity can be improved even in a state where hydroxyl groups partially remain on the surface of the magnetic body.
[0100] The amount of carbon derived from the silane compound in the surface-treated magnetic body A is preferably less than 0.5 mass %, and more preferably less than 0.4 mass %. The carbon content is preferably 0.2 mass % or more.
[0101] The above numerical ranges can be arbitrarily combined. In addition, the above numerical ranges can be adjusted by changing the surface treatment method of the magnetic body and the amount of the hydrophobic treatment agent added.
[0102] The surface of the magnetic body can be treated, for example, by the following method, but is not limited to this method.
[0103] In order to allow the hydrophobizing agent to react uniformly on the particle surface of the magnetic body to express hydrophobicity and at the same time to partially leave the hydroxyl groups on the surface of the magnetic body without being completely hydrophobized, the surface treatment is preferably performed dryly using a wheel kneader or a mill.
[0104] Here, as the wheel kneader, a Mix-Muller, a Multi-Mul, a Stotts mill, a backflow kneader, an Erich-mill, etc. can be used, and a Mix-Muller is preferably used.
[0105] When a wheel-shaped kneader or mill is used, three functions of compression, shearing and scraping can be exhibited.
[0106] By compression, the hydrophobic treatment agent between the particles of the magnetic body is pressed to the surface of the magnetic body, thereby can improve the adhesion and reactivity with the particle surface. By applying shearing force to each hydrophobic treatment agent and the magnetic body with shearing action, the hydrophobic treatment agent can be extended and the particles of the magnetic body can be split to dissolve the aggregate. In addition, with the spatula effect, the hydrophobic treatment agent existing on the magnetic particle surface can be evenly spread as with a spatula.
[0107] As a result of the continuous and repeated manifestation of the above three effects, the surface of each magnetic particle can be uniformly treated while the particle aggregate is broken apart and separated into individual particles without being aggregated.
[0108] Generally, a hydrophobizing agent represented by formula (I) having a relatively large number of carbon atoms is unlikely to uniformly treat the particle surface of the magnetic body at the molecular level because the agent molecules are large and bulky, but treatment by the above method is preferred because the treatment can be stably performed.
[0109] When the surface treatment of the magnetic body is performed by using the hydrophobizing agent represented by formula (I) through a wheel kneader or a mill, a particle surface of the magnetic body on which portions reacted with the hydrophobizing agent and residual unreacted hydroxyl groups alternately exist and coexist can be formed.
[0110] By setting the particle surface of the magnetic body in such a state, it is possible to improve the hydrophobicity and impart a certain water absorption. In addition, by such a method, for example, the dipole interaction term a of the Hansen solubility parameter of the surface-treated magnetic body A can be adjusted to the above range.
[0111] Meanwhile, when the surface treatment is performed by a wet method such as paddle stirring, it is difficult to obtain the above-mentioned compression action and shearing action, and it is difficult to exert water absorption.
[0112] When the surface treatment is carried out by a device having only a stirring action such as a Henschel mixer, it is also difficult to exhibit a certain water absorption property although this is a dry treatment.
[0113] The toner particles preferably include a resin C other than the binder resin.
[0114] Furthermore, the resin C is preferably a non-crystalline resin.
[0115] Here, the non-crystalline resin is a resin in which no clear endothermic peak (melting point) is observed in differential scanning calorimetry (DSC).
[0116] When the dipole interaction term of the Hansen solubility parameter of resin C is taken as c (unit: MPa 1 / 2 ), c is preferably 5.80 to 6.60, and more preferably 6.00 to 6.30. c can be controlled by changing the kind of monomer forming resin C.
[0117] The glass transition temperature (Tg) of the resin C is preferably 60.0°C to 90.0°C, and more preferably 70.0°C to 82.0°C.
[0118] The resin C is preferably a non-crystalline polyester resin, and is also preferably a non-crystalline polyester resin including an isosorbide unit represented by the following formula (1).
[0119]
[0120] It is more preferable that the resin C is a non-crystalline polyester resin including an isosorbide unit, because the affinity between the surface-treated magnetic body A and the resin C is improved. This is apparently because isosorbide has a structure in which oxygen atoms are oriented more outward than in conventionally used alcohol monomers (e.g., alkylene oxide adducts of bisphenol A), thereby easily forming hydrogen bonds with the surface-treated magnetic body A.
[0121] It is preferred that the amount of the isosorbide unit in the resin C is 0.1 mol% to 30.0 mol% because the effect of the above-mentioned hydrogen bond is more significant and the affinity with the surface-treated magnetic body A tends to be higher. It is also preferred that the amount of the isosorbide unit in the resin C is 30.0 mol% or less because the developing performance is easily maintained even under high temperature and high humidity. The amount of the isosorbide unit in the resin C is more preferably 0.1 mol% to 5.0 mol%.
[0122] The non-crystalline polyester resin can be prepared by polycondensation of a polycarboxylic acid (a divalent or trivalent or higher carboxylic acid), an anhydride or a lower alkyl ester thereof, and a polyol (a divalent or trivalent or higher alcohol). When the polyol includes isosorbide, a non-crystalline polyester resin including an isosorbide unit represented by the above formula (1) can be obtained. Specifically, such a resin can be prepared by a dehydration condensation method at a reaction temperature of 180° C. to 260° C. in a nitrogen atmosphere at a composition ratio of a carboxyl group residue.
[0123] Examples of monomers that can be used in the production of the non-crystalline polyester resin include conventionally known divalent or trivalent or higher carboxylic acids and conventionally known divalent or trivalent or higher alcohols. Specific examples of these monomers are listed below.
[0124] Examples of the dicarboxylic acid include dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,13-tridecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,16-hexadecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, phthalic acid, isophthalic acid, terephthalic acid, dicarboxylic acids such as dodecenylsuccinic acid, anhydrides thereof or lower alkyl esters thereof, and aliphatic unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, citraconic acid, etc. Lower alkyl esters and anhydrides of these dicarboxylic acids may also be used.
[0125] Examples of the trivalent or higher carboxylic acid include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, anhydrides thereof, lower alkyl esters thereof, and the like.
[0126] These may be used alone or in combination of two or more.
[0127] Examples of the diol include alkylene glycols (1,2-ethanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosandiol); alkylene ether glycols (polyethylene glycol and polypropylene glycol); alicyclic glycols (1,4-cyclohexanedimethanol); bisphenols (bisphenol A); alkylene oxide (ethylene oxide and propylene oxide) adducts of alicyclic glycols, and alkylene oxide (ethylene oxide and propylene oxide) adducts of bisphenols (alkylene oxide adducts of bisphenol A).
[0128] The alkyl moiety of the alkylene glycol and the alkylene ether glycol may be linear or branched. Alkylene glycols having a branched structure can also be preferably used.
[0129] In addition, an aliphatic diol having a double bond may be used. Examples of the aliphatic diol having a double bond include the following compounds.
[0130] 2-butene-1,4-diol, 3-hexene-1,6-diol, and 4-octene-1,8-diol.
[0131] In addition, examples of the trivalent or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and the like.
[0132] These may be used alone or in combination of two or more.
[0133] For the purpose of adjusting the acid value and the hydroxyl value, monoacids such as acetic acid and benzoic acid, and monoalcohols such as cyclohexanol and benzyl alcohol may be used as required.
[0134] It is preferred that the alcohol component includes at least one selected from the group consisting of bisphenols and alkylene oxide adducts of bisphenols.
[0135] The amount of the resin C is preferably 1.5 parts by mass to 10.0 parts by mass, and more preferably 3.0 parts by mass to 6.0 parts by mass, relative to 100.0 parts by mass of the binder resin or the polymerizable monomer capable of forming the binder resin.
[0136] It is preferred that the toner particles include a crystalline material D.
[0137] When the dipole interaction term of the Hansen solubility parameter of the crystalline material D is taken as d (unit: MPa 1 / 2 ), d is preferably 0.50 to 2.50, and more preferably 1.10 to 2.10. d can be controlled by changing the kind of monomer constituting the crystalline material D.
[0138] The melting point of the crystalline material D is preferably 60.0°C to 75.0°C, and more preferably 65.0°C to 70.0°C.
[0139] From the viewpoint of low-temperature fixing property, it is preferred that the crystalline material D includes a crystalline polymer compound having an ester bond.
[0140] The amount of the crystalline material D may be 2.0 parts by mass to 35.0 parts by mass, and more preferably 5.0 parts by mass to 30.0 parts by mass, relative to 100.0 parts by mass of the binder resin or the polymerizable monomer capable of forming the binder resin.
[0141] The crystalline material D may include wax having an ester bond.
[0142] Here, the wax is a wax in which a clear endothermic peak (melting point) is observed in differential scanning calorimetry (DSC).
[0143] The wax is not particularly limited as long as it has an ester bond and crystallinity, and known waxes can be used. Examples of the wax include natural waxes such as carnauba wax, candelilla wax, etc., and derivatives thereof, and ester waxes.
[0144] Here, the derivatives include oxides, block copolymers with vinyl monomers, and graft-modified products.
[0145] Examples of ester waxes include monoester compounds having one ester bond in one molecule, and polyfunctional ester compounds such as diester compounds having two ester bonds in one molecule, tetrafunctional ester compounds having four ester bonds in one molecule, hexafunctional ester compounds having six ester bonds in one molecule, and the like.
[0146] The wax preferably includes at least one compound selected from the group consisting of monoester compounds and diester compounds.
[0147] Among them, the monoester compound is more excellent in low-temperature fixability because the ester compound tends to be linear and has high compatibility with the styrene-based resin.
[0148] Specific examples of the monoester compound include waxes mainly comprising fatty acid esters, such as carnauba wax, montanic acid ester wax, etc.; compounds obtained by partially or completely removing the acid component from such aliphatic esters, such as deoxidized carnauba wax, etc.; compounds obtained by subjecting vegetable oils and fats to hydrogenation, etc.; methyl ester compounds having a hydroxyl group; and saturated fatty acid monoesters, such as stearyl stearate, behenyl stearate, behenyl behenate, etc.
[0149] Specific examples of the diester include dibehenyl sebacate, nonanediol dibehenate, behenyl terephthalate, stearyl terephthalate and the like.
[0150] In addition, one kind of wax may be used alone, or two or more kinds may be used in combination.
[0151] In addition, from the viewpoint of low-temperature fixability, the crystalline material D may include a crystalline polyester.
[0152] The crystalline polyester is a polyester in which a clear endothermic peak (melting point) is observed in differential scanning calorimetry (DSC).
[0153] The crystalline polyester can be exemplified by a polycondensate of an alcohol component including an aliphatic diol and an acid component including an aliphatic dicarboxylic acid.
[0154] Among them, a polycondensate of an alcohol component including an aliphatic diol having 2 to 12 carbon atoms and an acid component including an aliphatic dicarboxylic acid having 2 to 12 carbon atoms is preferred.
[0155] Examples of the aliphatic diol having 2 to 12 carbon atoms include the following compounds.
[0156] 1,2-ethanediol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol.
[0157] In addition, an aliphatic diol having a double bond may be used. Examples of the aliphatic diol having a double bond include the following compounds.
[0158] 2-butene-1,4-diol, 3-hexene-1,6-diol, and 4-octene-1,8-diol.
[0159] Examples of the aliphatic dicarboxylic acid having 2 to 12 carbon atoms include the following compounds.
[0160] Oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, and 1,12-dodecanedicarboxylic acid. Lower alkyl esters and anhydrides of these aliphatic dicarboxylic acids may also be used.
[0161] Among them, sebacic acid, adipic acid, and 1,10-decanedicarboxylic acid and lower alkyl esters and anhydrides thereof are preferred.These may be used alone or in mixture of two or more.
[0162] In addition, aromatic dicarboxylic acids can also be used. Examples of aromatic dicarboxylic acids include the following compounds.
[0163] Terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid and 4,4'-biphenyl dicarboxylic acid.
[0164] Among them, terephthalic acid is preferable since it is easily available and easily forms a polymer having a low melting point.
[0165] Furthermore, dicarboxylic acids having a double bond may also be used. Dicarboxylic acids having a double bond may be suitably used to suppress hot offset during fixing because the entire resin can be crosslinked by utilizing the double bond of the acid.
[0166] The dicarboxylic acid can be exemplified by fumaric acid, maleic acid, 3-hexenedioic acid, and 3-octenedioic acid. Other examples include lower alkyl esters and anhydrides thereof. Among them, fumaric acid and maleic acid are preferred.
[0167] The production method of the crystalline polyester is not particularly limited, and the crystalline polyester can be produced by a general polyester polycondensation method in which an acid component and an alcohol component are reacted. Depending on the kind of monomer, the crystalline polyester can be produced by using, for example, a direct polycondensation method or an ester exchange method.
[0168] The toner particles preferably include the crystalline material E.
[0169] When the dipole interaction term of the Hansen solubility parameter of the crystalline material E is taken as e (unit: MPa 1 / 2 ), e is preferably 0.00 to 1.50, and more preferably 0.00 to 0.50. e can be controlled by changing the kind of monomer constituting the crystalline material E.
[0170] The melting point of the crystalline material E is preferably 65.0°C to 80.0°C, and more preferably 68.0°C to 77.0°C.
[0171] The crystalline material E can be exemplified by petroleum waxes such as paraffin wax, microcrystalline wax, caprolactam and the like and derivatives thereof, hydrocarbon waxes obtained by the Fischer-Tropsch process and derivatives thereof, polyolefin waxes represented by polyethylene and polypropylene and derivatives thereof.
[0172] Among them, paraffin wax is preferable. When the crystalline material E is paraffin wax, the releasability between the fixing film and the toner during film fixing is improved. Specific examples of the paraffin wax include, but are not limited to, HNP-51 (manufactured by Nippon Seiro Co., Ltd.).
[0173] The amount of the crystalline material E is preferably 5.0 parts by mass or less, and more preferably 3.0 parts by mass or less relative to 100.0 parts by mass of the binder resin or the polymerizable monomer capable of forming the binder resin. In addition, the amount of the crystalline material E is preferably 1.0 parts by mass or more. The numerical ranges can be combined arbitrarily. When the amount of the crystalline material E is within this range, the migration to the toner surface can be suppressed while ensuring the demoulding property during fixing.
[0174] The method for producing a toner disclosed herein is a method for producing a toner including toner particles including a binder resin, the method comprising:
[0175] a step (I) of dispersing a polymerizable monomer composition including a polymerizable monomer capable of forming a binder resin in an aqueous medium and forming particles of the polymerizable monomer composition in the aqueous medium, and
[0176] The step (II) of polymerizing the polymerizable monomers included in the particles of the polymerizable monomer composition, wherein
[0177] Toner is to make
[0178] (1) When the powder dynamic viscoelasticity measurement method is used, the measurement start temperature is set to 25° C., and the temperature increase rate is set to 20° C. / min, on a curve of storage elastic modulus E' in which temperature (° C.) is plotted as the abscissa and storage elastic modulus E' (Pa) is plotted as the ordinate, the temperature at which the storage elastic modulus E' at the start of measurement decreases by 50% is 60° C. to 90° C., and
[0179] (2) The load at the yield point of a displacement-load curve determined by a nanoindentation method, in which the load (mN) is plotted on the ordinate and the displacement (μm) is plotted on the abscissa, is 0.80 mN or more.
[0180] Here, the relationship between raw materials constituting toner particles will be described.
[0181] The toner particles preferably include the resin C, and the binder resin preferably includes the resin B.
[0182] Regarding the production method, the polymerizable monomer preferably includes a polymerizable monomer b capable of forming a resin B, and
[0183] The polymerizable monomer composition preferably includes a surface-treated magnetic body A that is surface-treated with a hydrophobizing agent including an organic compound having a hydrophobic group.
[0184] In addition, it is preferred that the polymerizable monomer composition includes resin C.
[0185] In addition, when the dipole interaction term of the Hansen solubility parameter of resin B is taken as b(MPa 1 / 2 ) and the dipole interaction term of the Hansen solubility parameter of resin C is taken as c(MPa 1 / 2 ), it is preferred to satisfy b <c。
[0186] When the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a(MPa 1 / 2 ), the dipole interaction term of the Hansen solubility parameter of resin B is taken as b(MPa 1 / 2), and the dipole interaction term of the Hansen solubility parameter of resin C is taken as c(MPa 1 / 2 ), it is preferred that the relationship represented by the following inequality (1) is satisfied:
[0187] b <a<c (1)。
[0188] By controlling the dipole interaction term of the Hansen solubility parameter so as to satisfy the relationship of inequality (1), the resin B, the surface-treated magnetic body A, and the resin C constituting the toner particles can be arranged at appropriate positions in the toner particles. In addition, it is considered that the occurrence of fogging can be suppressed while suppressing the occurrence of rear end offset even in long-term use under a high temperature and high humidity environment (e.g., temperature: 32.5° C. and relative humidity: 80%).
[0189] In addition, step (I) may further comprise:
[0190] a step of dispersing the surface-treated magnetic body A in a polymerizable monomer b capable of forming a resin B to obtain a surface-treated magnetic body dispersion, and
[0191] A step of dissolving the resin C in a surface-treated magnetic body dispersion to obtain a polymerizable monomer composition.
[0192] The polymerizable monomer composition may include the crystalline material D and / or the crystalline material E as required.
[0193] Due to differences in hydrophobicity and specific gravity, the resin, polymerizable monomer, and magnetic body tend to be unevenly distributed even if the dissolving strength is increased.
[0194] By maintaining a balance in affinity among the resin B, the surface-treated magnetic body A, and the resin C that form the surface layer structure of the toner particles, the surface layer of the toner can be controlled to have a specific structure.
[0195] Specifically, the toner particles preferably have a core-shell structure in which the outermost layer of the toner includes the resin C, the second layer is a shell including the surface-treated magnetic body A, and the core includes the resin B.
[0196] When the above three compounds satisfy the relationship of inequality (1), a specific shell structure is easily formed. As a result, the load corresponding to the yield point can be easily controlled within the above range.
[0197] Next, the affinity between the raw materials constituting the toner particles will be described.
[0198] When the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a(MPa 1 / 2 ),
[0199] The dipole interaction term of the Hansen solubility parameter of resin B is taken as b(MPa 1 / 2 ),
[0200] The dipole interaction term of the Hansen solubility parameter of resin C is taken as c(MPa 1 / 2 ), it is preferred that the following inequalities (2) and (3) are satisfied:
[0201] |ba|≤1.10 (2)
[0202] |ca|≤4.60 (3).
[0203] Regarding inequality (2), when the value of |ba| is 1.10 or less, the affinity between the surface-treated magnetic body A and the resin B is improved, and the adhesion between the materials is easily enhanced. Therefore, the degradation of the toner can be suppressed even during long-term use. The value of |ba| is preferably 0.70 or less, more preferably 0.60 or less, and even more preferably 0.50 or less. The value of |ba| is preferably 0.20 or more. The numerical ranges can be arbitrarily combined.
[0204] In addition, regarding inequality (3), when the value of |ca| is 4.60 or less, the affinity between the resin C and the surface-treated magnetic body A is improved, and the adhesion between the materials is easily enhanced. Therefore, the degradation of the toner can be suppressed even during long-term use. The value of |ca| is preferably 4.40 or less, and more preferably 4.20 or less. The value of |ca| is preferably 1.20 or more. The numerical ranges can be arbitrarily combined.
[0205] When the dipole interaction term of the Hansen solubility parameter of the crystalline material D is taken as d(MPa 1 / 2 ), and the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a(MPa 1 / 2 ), the following inequality (4) is satisfied:
[0206] |da|≤0.75 (4).
[0207] By controlling the dipole interaction term of the Hansen solubility parameter so as to satisfy the relationship of inequality (4), the crystalline material D can be kept inside the toner without migrating to the toner surface except during fixing. This is preferred from the viewpoint of storage stability. Preferably, |da|≤0.70, more preferably, |da|≤0.35, even more preferably, |da|≤0.30, and particularly preferably, |da|≤0.25. In addition, |da|≥0.05 is preferred, and |da|≥0.10 is more preferred. The numerical ranges can be arbitrarily combined.
[0208] When the dipole interaction term of the Hansen solubility parameter of the crystalline material E is taken as e(MPa 1 / 2 ), and the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a(MPa 1 / 2 ), the following inequality (5) is satisfied:
[0209] |ea|≥1.50 (5).
[0210] Preferably, |ea|≥1.80, more preferably, |ea|≥2.00. Preferably, |ea|≤2.10. Any combination of numerical ranges is possible.
[0211] In a cross section of the toner observed with a scanning electron microscope,
[0212] When the number of toners having domains of crystalline material D having a major diameter of 500 nm or more is taken as B1, and the number of toners not having domains of crystalline material D having a major diameter of 500 nm or more is taken as C1, the following inequality (6) is satisfied:
[0213] B1 / (B1+C1)≤0.20 (6).
[0214] Preferably, B1 / (B1+C1) is 0.15 or less, more preferably, 0.10 or less. Preferably, B1 / (B1+C1) is 0.00 or more. Any combination of numerical ranges is possible.
[0215] By setting B1 / (B1+C1) to 0.20 or less, the number of domains of the crystalline material D having a small interface with the binder resin is reduced, and efficient fixing is possible. As a result, low-temperature fixability and gloss uniformity are improved. B1 / (B1+C1) can be controlled by changing the kind or combination of the crystalline material D, or by manufacturing toner particles using a manufacturing method in which the crystalline material D is rapidly cooled and crystallized from a state in which the crystalline material D is compatible with the binder resin.
[0216] In a cross section of the toner observed with a scanning electron microscope,
[0217] When the area ratio of the surface-treated magnetic body A within a range of 200 nm or less from the cross-sectional contour of the toner particle toward the center of gravity of the toner particle in the cross section is taken as A1,
[0218] The area ratio A1 is preferably 35% or more, or preferably 38% or more, and even more preferably 45% or more. In addition, the area ratio A1 is preferably 80% or less, and more preferably 75% or less. The numerical ranges can be arbitrarily combined. The area ratio A1 can be, for example, 35% to 80%.
[0219] When the area ratio A1 is 35% or more, the load corresponding to the yield point is easily adjusted to the above range, and the brittle fracture of the toner itself is easily suppressed. At the same time, when the area ratio A1 is 80% or less, the low-temperature fixability is not easily impaired. When the area ratio is within the above range, both low-temperature fixability and durability can be achieved at a high level.
[0220] The area ratio A1 can be controlled by changing the amount of the magnetic body, the type of medium used in toner production, the type of the magnetic body, and the type of the surface treatment agent.
[0221] The toner particles may include a charge control agent. The toner is preferably a negatively chargeable toner.
[0222] As the charge control agent for negative charging, organic metal complexes and chelate compounds are effective, and examples thereof include monoazo metal complexes; acetylacetone metal complexes; metal complexes of aromatic hydroxycarboxylic acids or aromatic dicarboxylic acids, and the like.
[0223] Specific examples of commercially available products include Spilon Black TRH, T-77, T-95 (Hodogaya Chemical Industry Co., Ltd.) and S-34, S-44, S-54, E-84, E-88, and E-89 (Orient Chemical Industry Co., Ltd.).
[0224] The charge control agents may be used alone or in combination of two or more.
[0225] From the viewpoint of charge amount, the amount of the charge control agent is preferably 0.1 to 10.0 parts by mass, and more preferably 0.1 to 5.0 parts by mass, relative to 100.0 parts by mass of the binder resin or the polymerizable monomer capable of forming the binder resin.
[0226] The toner particles may include a crosslinking agent. The crosslinking agent is preferably added in an amount of 0.01 to 5.00 parts by mass relative to 100.0 parts by mass of the binder resin or the polymerizable monomer capable of forming the binder resin.
[0227] As the crosslinking agent, compounds having two or more polymerizable double bonds can be mainly used. Specifically, for example, aromatic divinyl compounds such as divinylbenzene, divinylnaphthalene, etc.; carboxylates having two double bonds such as ethylene glycol diacrylate, ethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, 1,6-hexanediol diacrylate, etc.; divinyl compounds such as divinylaniline, divinyl ether, divinyl sulfide, divinyl sulfone, etc.; compounds having three or more vinyl groups can be used. These can be used alone or in a mixture of two or more.
[0228] The production method of the toner is not limited to the above-mentioned suspension polymerization method, and any of a dry production method (eg, kneading pulverization method, etc.) and a wet production method (eg, emulsion aggregation method, solution suspension method, etc.) may be used.
[0229] Among them, it is preferred to use the above-mentioned suspension polymerization method. Specifically, for example, the following production method can be used, but it is not limited to this production method.
[0230] In the production of toner particles by suspension polymerization, a polymerization initiator may be used. A polymerization initiator having a half-life of 0.5 to 30 hours during the polymerization reaction is preferred. In addition, the amount of the polymerization initiator added is preferably 0.5 to 20 parts by mass relative to 100 parts by mass of the polymerizable monomer. In this case, a polymer having a maximum molecular weight between 5,000 and 50,000 can be obtained, and the toner particles can have preferred strength and appropriate melting characteristics.
[0231] Specific examples of polymerization initiators include azo or diazo polymerization initiators, such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, azobisisobutyronitrile, etc.; and peroxide polymerization initiators, such as benzoyl peroxide, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, lauroyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, di(2-ethylhexyl) peroxydicarbonate, di(sec-butyl) peroxydicarbonate, etc.
[0232] Among them, tert-butyl peroxypivalate is preferred.
[0233] The aqueous medium in which the polymerizable monomer composition is dispersed may include a dispersion stabilizer. As the dispersion stabilizer, known surfactants, organic dispersants, and inorganic dispersants may be used. Among them, inorganic dispersants are preferred because they have dispersion stability due to their steric hindrance, and therefore, even if the reaction temperature is changed, stability is hardly lost, washing is easy, and the toner is hardly adversely affected thereby.
[0234] Examples of such inorganic dispersants include polyvalent metal phosphates, such as trisodium phosphate, tricalcium phosphate, magnesium phosphate, aluminum phosphate, zinc phosphate, hydroxyapatite, etc.; carbonates, such as calcium carbonate, magnesium carbonate, etc.; inorganic salts, such as calcium metasilicate, calcium sulfate, barium sulfate, calcium chloride, etc.; inorganic compounds, such as calcium hydroxide, magnesium hydroxide, aluminum hydroxide, etc.
[0235] Relative to 100 parts by mass of polymerizable monomers, the usage amount of these inorganic dispersants is preferably 0.2 parts by mass to 20 parts by mass. In addition, dispersion stabilizers can be used alone or in combination of two or more. In addition, surfactants can be used in combination with the amount of 0.001 parts by mass to 0.1 parts by mass. When using these inorganic dispersants, they can be used as is, but in order to obtain finer particles, inorganic dispersant particles can be generated and used in an aqueous medium.
[0236] For example, in the case of tricalcium phosphate, an aqueous solution of sodium phosphate and an aqueous solution of calcium chloride can be mixed under high-speed stirring to produce water-insoluble calcium phosphate, and a more uniform and fine dispersion can be obtained. At this time, a water-soluble sodium chloride salt can be simultaneously produced as a byproduct, but it is preferred that the water-soluble salt is present in the aqueous medium because the dissolution of the polymerizable monomer in water is suppressed and it is less likely to produce an ultrafine toner by emulsion polymerization.
[0237] Examples of the surfactant include sodium dodecylbenzene sulfate, sodium tetradecyl sulfate, sodium pentadecyl sulfate, sodium octyl sulfate, sodium oleate, sodium laurate, sodium stearate, potassium stearate and the like.
[0238] In the step of polymerizing the polymerizable monomer, the polymerization temperature is usually set to 40° C. or higher, preferably 50° C. to 90° C. When the polymerization is performed in this temperature range, the release agent to be sealed inside is precipitated by phase separation, and the internalization becomes more complete.
[0239] Thereafter, a cooling step of cooling from the reaction temperature of about 50° C. to 90° C. is performed to terminate the polymerization reaction step.
[0240] Here, by using the method described below, the existence state of the domain of the crystalline material D having a specific major axis in the cross section of the toner observed with a scanning electron microscope can be easily controlled within the above range.
[0241] For example, after polymerizing the polymerizable monomer to obtain resin particles, the temperature of the dispersion in which the resin particles are dispersed in the aqueous medium is increased to a temperature exceeding the melting point of the crystalline material D. However, when the polymerization temperature exceeds the melting point, this operation is not required.
[0242] After the temperature increase, the cooling step may be performed by cooling the dispersion to about room temperature at a cooling rate of 3° C. / min to 200° C. / min (preferably 3° C. / min to 150° C. / min) to increase the crystallinity of the crystalline material D.
[0243] By cooling at a specific speed, a toner satisfying inequality (6) can be easily produced.
[0244] After the cooling step, the dispersion may be heated to about 50° C. and subjected to heat treatment.
[0245] The heat treatment is preferably performed for about 1 hour to 24 hours, more preferably about 2 hours to 10 hours.
[0246] After the polymerization of the polymerizable monomer is completed, the obtained polymer particles are filtered, washed, and dried by a known method to obtain toner particles.
[0247] The toner can be obtained by mixing the following external additives with the toner particles and attaching the external additives to the surface of the toner particles. In addition, the obtained toner particles can be directly used as the toner. A classification step can also be introduced in the manufacturing process to cut the coarse powder and fine powder included in the toner particles.
[0248] If necessary, the toner particles may be mixed with an external additive for improving the fluidity and / or charging performance of the toner to form a magnetic toner. A known device such as a Henschel mixer may be used for mixing the external additive.
[0249] Examples of the external additive include inorganic fine particles having a primary particle number average particle diameter of 4 nm to 80 nm, and more preferably inorganic fine particles having a number average particle diameter of 6 nm to 40 nm. The external additive may be used alone or in combination of two or more.
[0250] When the inorganic fine particles are subjected to hydrophobic treatment, the charging performance and environmental stability can be further improved. Examples of the treating agent used in the hydrophobic treatment include organosilicon varnishes, various modified organosilicon varnishes, silicone oils, various modified silicone oils, silane compounds, silane coupling agents, other organosilicon compounds, organotitanium compounds, etc. The treating agent can be used alone or in combination of two or more.
[0251] The number average particle diameter of the primary particles of the inorganic fine particles can be calculated using an image of the toner magnified and photographed by a scanning electron microscope (SEM).
[0252] In the method of producing toner particles by suspension polymerization, generally, a polymerizable monomer obtained by appropriately adding the above-mentioned toner composition and uniformly dissolving or dispersing it with a disperser such as a homomixer, a ball mill, an ultrasonic disperser, etc. is preferably dispersed in an aqueous medium including a dispersant.
[0253] At this time, when a high-speed disperser such as a high-speed stirrer or an ultrasonic disperser is used, the particle size of the obtained toner particles becomes sharper. The time of adding the polymerization initiator may be the same as when other additives are added to the polymerizable monomer, or may be immediately before being dispersed in the aqueous medium. In addition, the polymerization initiator dissolved in the polymerizable monomer or solvent may be added immediately after granulation and before starting the polymerization reaction.
[0254] After granulation, stirring may be performed using a conventional stirrer to such an extent that the granules are maintained in a state and prevented from floating and settling.
[0255] Examples of inorganic fine particles include silica fine particles, titanium oxide fine particles, aluminum oxide fine particles, etc. As the silica fine particles, for example, both so-called dry silica produced by gas phase oxidation of silicon halide, called dry process silica or fumed silica, and so-called wet silica made from water glass or the like can be used.
[0256] However, there are fewer silanol groups on the surface and inside of the silica fine particles and there are fewer organic compounds such as Na2O and SO3 2- Dry silica obtained from the production residue is more preferred.
[0257] In the case of fumed silica, for example, composite fine particles of silica and other metal oxides can be obtained by using other metal halides such as aluminum chloride, titanium chloride, etc. together with silicon halide during the production process. The composite fine particles can also be used as inorganic fine particles.
[0258] The amount of the inorganic fine particles is preferably 0.1 parts by mass to 3.0 parts by mass relative to 100 parts by mass of the toner particles.The amount of the inorganic fine particles can be quantified using a fluorescent X-ray analyzer from a calibration curve prepared from a standard sample.
[0259] The toner particles may further include other additives within a range not causing substantial adverse effects.
[0260] Examples of other additives include lubricant powders such as fluorine resin powders, zinc stearate powders, and polyvinylidene fluoride powders; abrasives such as cerium oxide powders, silicon carbide powders, strontium titanate powders, etc.; anti-caking agents; etc. The additives may be used after the surface thereof is subjected to a hydrophobic treatment.
[0261] The glass transition temperature (Tg) of the toner is preferably 45.0°C to 65.0°C, and more preferably 50.0°C to 65.0°C.
[0262] When the glass transition temperature is within the above range, both storage stability and low temperature fixability can be achieved at a high level. The glass transition temperature can be controlled by the composition of the binder resin, the kind of crystalline material, the molecular weight of the binder resin, and the like.
[0263] The weight average particle diameter (D4) of the toner is preferably 3.0 μm to 8.0 μm, and more preferably 5.0 μm to 7.7 μm.
[0264] By setting the weight average particle diameter (D4) of the toner within the above range, it is possible to sufficiently satisfy dot reproducibility while improving the operability of the toner.
[0265] Furthermore, the ratio (D4 / D1) of the weight average particle diameter (D4) to the number average particle diameter (D1) of the magnetic toner is preferably less than 1.25.
[0266] The measurement methods of physical properties are described below.
[0267] <Measurement Method of Dipole Interaction Term of Hansen Solubility Parameter>
[0268] When the raw materials of the toner are obtained, first, the molecular structure of the raw material of the hydrophobizing agent is specified for the surface-treated magnetic body A, and the molecular structure of each raw material is specified for the resin B and the resin C. The means for specifying the molecular structure is not particularly limited, but, for example, a technique such as a safety data sheet (SDS) can be used.
[0269] Based on the specified molecular structure, the dipole interaction term of the Hansen solubility parameter is calculated from the calculation software. The calculation software is not particularly limited. For example, HSPiP (which can be obtained from http: / / pirika.com / JP / HSP / index.html get).
[0270] When the raw materials cannot be directly obtained, or an existing toner is used as a sample, the dipole interaction term of the Hansen solubility parameter is calculated by identifying the constituent materials of the toner and the molecular structure of the constituent materials using analytical instruments such as a nuclear magnetic resonance device (NMR) and gas chromatography / mass spectrometry (GC / MS).
[0271] <Method for measuring weight average particle diameter (D4) and number average particle diameter (D1) of toner>
[0272] The weight average particle diameter (D4) and the number average particle diameter (D1) of the toner are calculated as follows.
[0273] The Coulter Counter Multisizer, a precision particle size distribution measuring instrument based on the pore resistance method and equipped with a 100-μm aperture tube, was used to measure the particle size distribution of the sample. " (manufactured by Beckman Coulter, Inc.) was used as a measuring device. Dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.) was used to set measurement conditions and analyze measurement data. Measurement was performed with 25,000 effective measurement channels.
[0274] A solution prepared by dissolving special grade sodium chloride in ion exchange water to a concentration of about 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.) can be used as the aqueous electrolytic solution used for measurement.
[0275] Prior to measurement and analysis, the dedicated software was set up as follows.
[0276] In the "Change Standard Measurement Method (SOM)" screen of the dedicated software, set the total count of the control mode to 50,000 particles, the number of measurements to 1, and the value obtained using "Standard Particles 10.0 μm" (manufactured by Beckman Coulter, Inc.) as the Kd value. The threshold and noise level are automatically set by pressing "Threshold / Noise Level". Further, set the current to 1,600 μA, the gain to 2, the electrolyte to ISOTON II, and check "Orifice Tube Flush" for "After Each Measurement".
[0277] In the "Pulse to Size Conversion Settings" screen of the dedicated software, the cell spacing was set to logarithmic size, the size cell was set to 256-size cell, and the size range was set to 2 μm to 60 μm.
[0278] The specific measurement method is described below.
[0279] (1) Place approximately 200 mL of the above-mentioned electrolytic aqueous solution in a 250 mL round-bottom glass beaker dedicated to Multisizer 3, place the beaker on the sample stage, and stir it counterclockwise at 24 revolutions per second with a stirring rod. Use the "mouth tube flushing" function of the dedicated software to remove dirt and bubbles in the mouth tube.
[0280] (2) About 30 mL of the electrolytic aqueous solution was placed in a 100 mL flat-bottomed beaker made of glass. Then, about 0.3 mL of a dilution prepared by diluting "Contaminon N" (a 10% by mass aqueous solution of a neutral detergent for washing precision measuring instruments at pH 7, composed of a nonionic surfactant, an anionic surfactant and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) by about 3 times the mass with ion-exchanged water was added thereto as a dispersant.
[0281] (3) An ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Co., Ltd.) having a power output of 120 W and in which two oscillators having an oscillation frequency of 50 kHz were built with a phase shift of 180 degrees was prepared. A total of about 3.3 L of ion-exchanged water was placed in the water tank of the ultrasonic disperser, and about 2 mL of Contaminon N was added to the water tank.
[0282] (4) The beaker in (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is started. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolytic aqueous solution in the beaker is maximized.
[0283] (5) While the electrolytic aqueous solution in the beaker of (4) is irradiated with ultrasonic waves, about 10 mg of toner is gradually added to the electrolytic aqueous solution and dispersed therein. Then, the ultrasonic dispersion treatment is further continued for 60 seconds. During the ultrasonic dispersion treatment, the water temperature in the water tank is appropriately adjusted to a temperature of 10° C. to 40° C.
[0284] (6) The electrolytic aqueous solution of (5) above in which the toner is dispersed is dropped into the round-bottom beaker of (1) above set in the sample stage by using a pipette, and the measurement concentration is adjusted to about 5%. Then, measurement is performed until the number of measured particles reaches 50,000.
[0285] (7) The measurement data is analyzed using the dedicated software attached to the device, and the weight average particle diameter (D4) and the number average particle diameter (D1) are calculated. When the graph / volume % is set in the dedicated software, the "average diameter" on the "analysis / volume statistics (arithmetic mean)" screen obtained is the weight average particle diameter (D4), and when the graph / number % is set in the dedicated software, the "average diameter" on the "analysis / number statistics (arithmetic mean)" screen obtained is the number average particle diameter (D1).
[0286] <Method for measuring the peak temperature (melting point) of the maximum endothermic peak>
[0287] The peak temperature of the maximum endothermic peak of a sample such as a toner or a resin is measured by using a differential scanning calorimeter (DSC) Q2000 (manufactured by TA Instruments) under the following conditions.
[0288] Heating rate: 10℃ / min
[0289] Measurement start temperature: 20°C
[0290] Measurement end temperature: 180℃
[0291] The melting points of indium and zinc are used for temperature correction of the device detection unit, and the melting heat of indium is used for correction of the calorific value.
[0292] Specifically, 5 mg of the sample was accurately weighed and placed in an aluminum pan, and measured once. An empty aluminum pan was used as a reference. The peak temperature of the maximum endothermic peak in the DSC curve was determined at this time. The peak temperature of the maximum endothermic peak was taken as the melting point.
[0293] <Measurement Method of Glass Transition Temperature (Tg)>
[0294] The glass transition temperature of a sample such as a toner, a resin, etc. is determined using a reversing heat flow curve at a temperature increase obtained by differential scanning calorimetry of the peak temperature of the maximum endothermic peak, and is the temperature (°C) at a point where a straight line equidistant in the longitudinal direction from a straight line obtained by extending the base line before and after the specific heat change, and a curve of a step-like change portion of the glass transition in the reversing heat flow curve intersect each other.
[0295] <Method for measuring weight average molecular weight (Mw) and peak molecular weight (Mp)>
[0296] The peak molecular weight (Mp) of samples such as resins and other materials is measured by gel permeation chromatography (GPC) in the following manner.
[0297] (1) Preparation of measurement samples
[0298] The sample and tetrahydrofuran (THF) are mixed at a concentration of 5.0 mg / mL, and allowed to stand at room temperature for 5 to 6 hours, and then fully shaken, and THF and the sample are fully mixed until the sample no longer agglomerates. The mixture is further allowed to stand at room temperature for more than 12 hours. At this time, the time from the mixing of the sample and THF to the termination of standing is set to more than 72 hours to obtain the tetrahydrofuran (THF) soluble matter of the sample.
[0299] Thereafter, the mixture was filtered through a solvent-resistant membrane filter (pore diameter: 0.45 μm to 0.50 μm, Maishori Disk H-25-2 [manufactured by Tosoh Corporation]) to obtain a sample solution.
[0300] (2) Sample measurement
[0301] The measurement was performed under the following conditions by using the obtained sample solution.
[0302] Apparatus: High-speed GPC apparatus LC-GPC 150C (manufactured by Waters Corp.)
[0303] Column: 7 sets of Shodex GPC KF-801, 802, 803, 804, 805, 806 and 807 (manufactured by Showa Denko KK)
[0304] Mobile phase: THF
[0305] Flow rate: 1.0mL / min
[0306] Column temperature: 40°C
[0307] Sample injection volume: 100 μL
[0308] Detector: RI (refractive index) detector
[0309] When the molecular weight of a sample is measured, the molecular weight distribution of the sample is calculated from the relationship between the logarithmic value of a calibration curve prepared from several monodisperse polystyrene standard samples and the counts.
[0310] The standard polystyrene samples used for preparing the calibration curve were manufactured by Pressure Chemical Co. or Toyo Soda Kogyo Co., Ltd. and had a molecular weight of 6.0×10 2 , 2.1×10 3 4.0×10 3 , 1.75×10 4 , 5.1×10 4 , 1.1×10 5 , 3.9×10 5 , 8.6×10 5 , 2.0×10 6 , and 4.48×10 6 .
[0311] <Method for measuring the load used as the yield point by the nanoindentation method>
[0312] PICODENTOR HM500 manufactured by Fisher Instrument Co., Ltd. was used to measure the load corresponding to the yield point by the nanoindentation method. Software WIN-HCU was used. A Vickers hardness tester indenter (angle: 130°) was used as an indenter.
[0313] The measurement includes a step of pushing the indenter for a predetermined time until a predetermined load is obtained (hereinafter, referred to as an "indentation step"). In this measurement, the load application speed is changed by changing the setting time and the load.
[0314] First, focus the microscope on the camera screen connected to the microscope displayed on the software. Place a glass plate (hardness: 3,600 N / mm 2 ) is used as an object for focusing. At this time, focusing is performed in sequence from an objective lens with a magnification of 5 to an objective lens with a magnification of 20 and an objective lens with a magnification of 50. Thereafter, adjustment is performed with an objective lens with a magnification of 50.
[0315] Next, the "approach parameter setting" operation is performed using the glass plate focused as described above, and the Z-axis alignment of the indenter is performed. Thereafter, the glass plate is replaced with an acrylic plate, and the "indenter cleaning" operation is performed. The "indenter cleaning" operation is to clean the tip of the indenter with a cotton swab moistened with ethanol and to make the indenter position indicated by the software consistent with the indenter position on the hardware, that is, the XY axis alignment operation of the indenter.
[0316] Thereafter, replace the acrylic plate with the slide glass with the toner attached, and focus the microscope on the toner to be measured. The method used to attach the toner to the slide glass is as follows:
[0317] First, the toner to be measured is attached to the tip of a cotton swab, and the excess toner is sifted off at the edge of the bottle. Then, while pressing the cotton swab shaft against the edge of a slide glass, the toner attached to the cotton swab is knocked off to obtain a toner monolayer on the slide glass.
[0318] Then, the slide glass to which the toner monolayer has been attached as described above is set on the microscope, the microscope is focused on the toner with an objective lens of magnification 50, and the tip of the indenter is set on the software to the center of the toner particle. The toner to be selected is limited to particles with a major diameter and a minor diameter of about D4 (μm) ± 1.0 μm.
[0319] The measurement was performed by carrying out an indentation step under the following conditions.
[0320] (Indentation step 1)
[0321] -Maximum indentation load = 1.25mN
[0322] - Indentation time = 300 seconds
[0323] Under the above conditions, an indentation speed of 0.42 μN / s can be set.
[0324] In the indentation step, a load-displacement curve in which load (mN) is plotted as the ordinate and displacement (μm) is plotted as the abscissa is obtained. Next, using spreadsheet software (Microsoft Excel), the slope of each curve of the obtained load-displacement curve is determined, thereby obtaining a differential curve obtained by differentiating the load-displacement curve for a small load. From the obtained differential curve, the load having the maximum value is determined, and the load corresponding to the yield point is obtained. The displacement at the initially measured positive load is defined as the initial value of the displacement.
[0325] The above measurement is performed on 30 particles of the toner, and the arithmetic mean value is used.
[0326] During the measurement, the above-mentioned "indenter cleaning" operation (including XY axis alignment of the indenter) is always performed for each particle measurement.
[0327] <Method for measuring dynamic viscoelasticity of toner powder>
[0328] The measurement was performed using a dynamic viscoelasticity measuring apparatus DMA8000 (manufactured by Perkin Elmer Corp.).
[0329] Measuring fixture: Material bag (P / N: N533-0322)
[0330] A total of 80 mg of toner was inserted into the material bag, which was attached to the single cantilever and fixed by tightening the screw with a torque wrench.
[0331] Dedicated software "DMA Control Software" (manufactured by Perkin Elmer Corp.) was used for the measurement. The measurement conditions are as follows. From the curve of the storage elastic modulus E' obtained by the measurement (plotting temperature (°C) as the abscissa and the storage elastic modulus E' (Pa) as the ordinate), the temperature at which the storage elastic modulus E' at the start of the measurement (25°C) decreases by 50% is determined.
[0332] Furnace: Standard air furnace
[0333] Measurement Type: Temperature Scan
[0334] DMA Condition: Single Frequency / Distortion (G)
[0335] Frequency: 1Hz
[0336] Strain: 0.05mm
[0337] Measurement start temperature: 25°C
[0338] End temperature: 180℃
[0339] Heating rate: 20℃ / min
[0340] Deformation mode: single cantilever (B)
[0341] Cross-section: Rectangular (R)
[0342] Test piece size (length): 17.5 mm
[0343] Test piece size (width): 7.5 mm
[0344] Test piece size (thickness): 1.5 mm
[0345] <Measurement method of area ratio A1>
[0346] The method for measuring the surface unevenness of the magnetic body in the cross section of the toner observed with a transmission electron microscope (TEM) is as follows.
[0347] First, a TEM image of the toner is obtained by the following method.
[0348] <Cross-sectional observation of toner>
[0349] The cross-sectional observation of the toner with a transmission electron microscope (TEM) is performed as follows. The cross-sectional observation of the toner is performed by staining with ruthenium. For example, the crystalline resin or the like contained in the toner is more stained with ruthenium than the amorphous resin such as the binder resin, so that the contrast becomes clear and is conducive to observation. Since the amount of ruthenium atoms varies depending on the strength of the staining, the strongly stained part includes many of these atoms, does not pass through the electron beam, and becomes black on the observed image, and the weakly stained part easily passes through the electron beam and becomes white on the observed image.
[0350] First, the toner was spread on a cover glass (Matsunami Glass Co., Ltd., corner cover glass, square No. 1) to form a single layer, and an Os film (5 nm) and a naphthalene film (20 nm) were coated as a protective film by using an Osmium Plasma Coater (filgen, Inc., OPC80T).
[0351] Next, a PTFE tube (φ1.5 mm×φ3 mm×3 mm) was filled with a photocurable resin D800 (JEOL, Ltd.), and a cover glass was placed on the tube in such an orientation that the toner contacted the photocurable resin D800. After the resin was cured by irradiation with light in this state, the cover glass and the tube were removed to form a cylindrical resin in which the toner was embedded on the outermost surface.
[0352] The cylindrical resin was cut by using ULTRASONIC ULTRAMICROTOME (Leica Microsystems Inc., UC7) at a cutting speed of 0.6 mm / s at a distance from the outermost surface equal to the radius of the toner (4.0 μm when the weight average particle diameter (D4) is 8.0 μm) to open the cross section of the toner. Next, cutting was performed to obtain a film thickness of 250 nm and a thin sheet sample having a cross section of the toner was prepared. By cutting in this manner, a cross section of the center portion of the toner was obtained.
[0353] The obtained thin-section sample was stained for 15 minutes in RuO 4 gas under 500 Pa atmosphere using a vacuum electron staining device (filgen, Inc., VSC4R1H,) and TEM observation was performed using TEM (JEOL, Ltd., JEM2800).
[0354] An image with a TEM probe size of 1 nm and an image size of 1,024 pixels × 1,024 pixels was acquired. In addition, the contrast of the image field was adjusted to 1425, the brightness to 3750, and the contrast of the image control panel to 0.0, the brightness to 0.5, and the gamma to 1.00.
[0355] Next, the obtained TEM image was binarized using the image processing software "ImageJ" (available from https: / / imagej.Nih.gov / ij / ). Thereafter, the circle equivalent diameter (projected area circle equivalent diameter) was obtained from the binarized image of the cross section, and the cross section whose circle equivalent diameter value was within the range of ±5% of the number average particle size (D1) (μm) of the toner was selected.
[0356] From the TEM image of the corresponding particles, the area except those required for measurement was masked using "ImageJ", and the area of the uncovered area inside the toner outline and the total area of the magnetic body present in the uncovered area were calculated. A method for obtaining the area ratio A1 using this method will be specifically described below.
[0357] First, the obtained TEM image of the outline of the toner cross section (hereinafter, referred to as Image 1) is binarized so that the outline and the inside of the toner particle are white and the other background portion is black (hereinafter, referred to as Image 2).
[0358] Next, to calculate the magnification of the mask, the length per unit pixel in Image 1 is calculated. Then, from the calculated value, the number of pixels that fit within a range of 200 nm from the contour of the toner particle towards the center of gravity of the toner particle (hereinafter referred to as x1) is calculated. Similarly, the number of pixels that fit the toner particle diameter measured using the above method (hereinafter referred to as x2) is calculated. Then, the magnification M of the mask is calculated by the following:
[0359] M = (x2 - x1) / x2.
[0360] Next, Image 2 is reduced to the calculated magnification M (the reduced image is denoted as Image 3). In Image 3, the image is processed such that the contour and interior of the toner particle are black and the other background portions are transparent.
[0361] Next, Image 2 and Image 3 are superimposed. At this time, Image 2 and Image 3 are superimposed using the "Image Calculator" which is a function of "ImageJ", and an Image 4 is created in which the region within 200 nm from the contour of the toner particle towards the center of gravity of the toner particle is white and the other portions are black. The area S1 of the white region in Image 4 is measured.
[0362] Next, the created Image 4 and Image 1 are similarly superimposed using the "Image Calculator" to create an Image 5 in which the region other than the range within 200 nm from the contour of the toner particle towards the center of gravity of the toner particle is covered. Image 5 is binarized, and the area S2 occupied by the surface-treated magnetic body A within the range is measured.
[0363] Finally, the area ratio a1 is calculated as S2 / S1.
[0364] The above operations are performed on 100 toner particles, and the arithmetic mean of the 100 obtained area ratios a1 is defined as the area ratio A1.
[0365] <Calculation method of B1 / (B1 + C1)>
[0366] Observation is performed by the above method for observing the cross-section of the toner, and 50 toner particles with diameters within ±2.0 μm of the number average particle diameter are selected and their images are taken to obtain cross-sectional images.
[0367] Compared with the non-crystalline resin or magnetic body, the crystalline material is not stained with Ru and appears black to gray in the cross-sectional image.
[0368] From the 50 toner particles from which the cross-sectional images are obtained, the number of toner particles having domains of 500 nm or more is taken as B1, the number of toner particles not having domains of 500 nm or more is taken as C1, and the presence rate of toner particles having domains of 500 nm or more is determined by B1 / (B1 + C1).
[0369] <Method for measuring the amount of carbon derived from the silane compound in the surface-treated magnetic body A>
[0370] The carbon amount per unit weight of the surface-treated magnetic body A was measured using a carbon / sulfur analyzer (EMIA-320V) manufactured by HORIBA Co. The amount of carbon obtained by this operation was defined as the amount of carbon derived from the silane compound (unit: mass %). In the measurement, the sample loading amount when measured with EMIA-320V was set to 0.20 g, and a mixture of tungsten and tin was used as a combustion aid.
[0371] <Method for measuring the amount of crystalline material E>
[0372] When the raw material of the crystalline material E is not available, the separation operation is performed in the following manner.
[0373] First, the toner is dispersed in ethanol, which is a poor solvent for the toner, and the temperature is raised to a temperature exceeding the melting point of the crystalline material E. At this time, pressure is applied as needed. At this time point, the crystalline materials D and E exceeding the melting point have melted. Thereafter, a mixture of crystalline materials D and E can be collected from the toner by solid-liquid separation. By classifying this mixture of each molecular weight, the crystalline material E can be separated.
[0374] The amount of the crystalline material E is determined from the mass of the crystalline material E separated from the toner by the above method and the mass of the original toner.
[0375] Example
[0376] Hereinafter, the present disclosure will be specifically described with reference to Examples and Comparative Examples, but the present disclosure is not limited thereto. In Examples and Comparative Examples, all parts and percentages are based on mass unless otherwise specified.
[0377] <Production Example of Resin C1>
[0378] A total of 100 parts of a mixture obtained by mixing raw material monomers other than trimellitic anhydride in the loading amounts shown in Table 1 below, and 0.52 parts of tin di(2-ethylhexanoate) as a catalyst were placed in a polymerization tank equipped with a nitrogen introduction line, a dehydration line and a stirrer.
[0379] Next, after the inside of the polymerization tank was set to a nitrogen atmosphere, a polycondensation reaction was performed for 6 hours while heating at 200°C. Furthermore, after the temperature was raised to 210°C, trimellitic anhydride was added, the pressure in the polymerization tank was reduced to 40 kPa, and then a condensation reaction was further performed to obtain a non-crystalline polyester resin C1. Table 1 shows the Tg of the obtained non-crystalline polyester resin C1 and the dipole interaction term c of the Hansen solubility parameter.
[0380] <Production Example of Resins C2 and C3>
[0381] Non-crystalline polyester resin C2 and non-crystalline polyester resin C3 were produced by performing the same operation as the production of resin C1, using the loading amounts of the raw material monomers shown in Table 1. Table 1 shows the dipole interaction term c of the Hansen solubility parameter and the glass transition temperature (Tg) of the obtained non-crystalline polyester resin C2 and non-crystalline polyester resin C3.
[0382] [Table 1]
[0383]
[0384] The abbreviations in Table 1 are as follows.
[0385] BPA (2 mol PO): Bisphenol A propylene oxide 2 mol adduct
[0386] EG: Ethylene glycol
[0387] TPA: Terephthalic acid
[0388] TMA: trimellitic anhydride
[0389] <Production Example of Crystalline Material D1>
[0390] - 100.0 parts of sebacic acid
[0391] -1,9-nonanediol 100.0 parts
[0392] -Dibutyltin oxide 0.1 parts
[0393] The above materials were placed in a heated and dried two-necked flask, nitrogen was introduced into the container to maintain an inert atmosphere, and the temperature was raised while stirring. Thereafter, stirring was performed at 180° C. for 6 hours.
[0394] Thereafter, while continuing to stir, the temperature was gradually raised to 230° C. under reduced pressure and further maintained for 2 hours. When the mixture became viscous, the mixture was air-cooled to stop the reaction, thereby obtaining a crystalline material D1.
[0395] Table 2 shows the dipole interaction term d of the Hansen solubility parameter and the melting point obtained for the crystalline material D1.
[0396] <Crystalline Materials D2 to D4>
[0397] Table 2 shows crystalline materials D2 to D4 used in the present embodiment and comparative examples.
[0398] [Table 2]
[0399]
[0400] <Crystalline Material E>
[0401] Table 3 shows the crystalline material E used in the present example and the comparative example.
[0402] [Table 3]
[0403]
[0404] <Production Example of Magnetic Iron Oxide 1>
[0405] An aqueous solution containing ferrous hydroxide was prepared by mixing 1.0 equivalent of caustic soda solution (containing 1 mass % of sodium hexametaphosphate as P relative to Fe) with an aqueous solution of ferrous sulfate. While maintaining the pH of the aqueous solution at 9, air was blown into it to perform an oxidation reaction at 80° C. to prepare a slurry for generating seed crystals.
[0406] Next, an aqueous solution of ferrous sulfate was added to the slurry so that the equivalent relative to the initial alkali amount (sodium component of caustic soda) was 1.0 equivalent. The slurry was maintained at pH 8 to carry out oxidation reaction while blowing air, and the pH value was adjusted to 6 at the end of the oxidation reaction, followed by washing and drying to obtain magnetic iron oxide 1 in the form of spherical magnetite particles and a primary particle number average particle diameter of 200 nm.
[0407] <Production Example of Magnetic Iron Oxide 2>
[0408] Magnetic iron oxide 2 was obtained in the same manner as in the production example of magnetic iron oxide 1 except that the liquid temperature during the oxidation reaction in the production example of magnetic iron oxide 1 was changed from 80° C. to 65° C. Magnetic iron oxide 2 was in the form of spherical magnetite particles, and the number average particle diameter of primary particles was 300 nm.
[0409] <Production Example of Magnetic Iron Oxide 3>
[0410] Magnetic iron oxide 3 was obtained in the same manner as in the production example of magnetic iron oxide 1 except that the liquid temperature during the oxidation reaction in the production example of magnetic iron oxide 1 was changed from 80° C. to 74° C. Magnetic iron oxide 3 was in the form of spherical magnetite particles, and the number average particle diameter of primary particles was 260 nm.
[0411] <Production Example of Silane Compound 1>
[0412] A total of 30 parts of n-decyltrimethoxysilane were added dropwise to 70 parts of ion exchange water while stirring. Thereafter, the aqueous solution was maintained at a pH of 5.5 and a temperature of 55°C, and was dispersed for 120 min at a circumferential speed of 0.46 m / s using a dispersion blade to hydrolyze. Thereafter, the pH of the aqueous solution was adjusted to 7.0, and the solution was cooled to 10°C to stop the hydrolysis reaction. Thus, an aqueous solution (silane compound 1) comprising a hydrolyzate of n-decyltrimethoxysilane was obtained.
[0413] <Production Examples of Silane Compounds 2 to 4>
[0414] Silane Compounds 2 to 4 were obtained in the same manner as in the Production Example of Silane Compound 1, except that n-decyltrimethoxysilane was replaced with the raw materials shown in Table 4.
[0415] [Table 4]
[0416] Silane compounds raw materials Silane compound 1 n-Decyltrimethoxysilane Silane compound 2 n-Octyltrimethoxysilane Silane compound 3 n-Butyltrimethoxysilane Silane compound 4 n-Tetradecanetrimethoxysilane
[0417] <Production Example of Surface-treated Magnetic Body A1>
[0418] A total of 100 parts of the magnetic iron oxide 1 were put into a Simpson mixer mill (model MSG-0L, manufactured by SINTOKOGIO, LTD.) and pulverized for 30 min.
[0419] Thereafter, 0.94 parts of the silane compound 1 was added as a hydrophobizing agent into the apparatus, and the apparatus was operated for 1 hour to obtain a surface-treated magnetic body A1.
[0420] The obtained surface-treated magnetic body A1 had a spherical particle shape, and the number average particle diameter of primary particles was 200 nm.
[0421] Table 5 shows the dipole interaction term a of the Hansen solubility parameter and the physical properties of the obtained surface-treated magnetic body A1.
[0422] <Manufacturing of Surface-treated Magnetic Bodies A2, A3, and A4>
[0423] In the method for producing the surface-treated magnetic body A1, the type and amount of the silane compound were appropriately changed as shown in Table 5. Thus, surface-treated magnetic bodies A2, A3, and A4 were obtained. The particle shapes of the obtained surface-treated magnetic bodies A2, A3, and A4 were all spherical, and the number average particle diameters of the primary particles were 300 nm, 200 nm, and 200 nm, respectively.
[0424] Table 5 shows the dipole interaction term a of the Hansen solubility parameters and the physical properties of the obtained surface-treated magnetic bodies A2, A3, and A4.
[0425] [Table 5]
[0426]
[0427] <Manufacturing of Surface-treated Magnetic Body A5>
[0428] 100 parts of magnetic iron oxide 1 were placed in a Henschel mixer (Nippon Coke Industry Co., Ltd.), and silane compound 1 (1.12 parts) was added while being sprayed while being dispersed at a rotation speed of 34.5 m / s. Next, after being dispersed in the same state for 10 minutes, the magnetic iron oxide 1 on which the silane compound 1 was adsorbed was taken out, and the magnetic iron oxide 1 was dried while being allowed to stand at 160° C. for 2 hours, and a polycondensation reaction of the silane compound 1 was performed. Thereafter, the mixture was passed through a sieve with an opening of 100 μm to obtain a surface-treated magnetic body A5.
[0429] The obtained surface-treated magnetic body A5 had a spherical particle shape, and the number average particle diameter of primary particles was 200 nm. Table 6 shows the dipole interaction term a of the Hansen solubility parameter and the physical properties of the obtained surface-treated magnetic body A5.
[0430] [Table 6]
[0431]
[0432] <Manufacturing of Surface-treated Magnetic Body A6>
[0433] A total of 100 parts of magnetic iron oxide 3 and 1.00 parts of silane compound 3 are dispersed in an aqueous medium, fully stirred, and hydrophobized by a wet method. The generated hydrophobic magnetic iron oxide is washed, filtered and dried by a conventional method. Thereafter, a magnetic body passing through a sieve with an opening of 100 μm is obtained as a surface-treated magnetic body A6. The surface-treated magnetic body A6 obtained has a spherical particle shape, and the number average particle size of the primary particles is 260 nm. Table 7 shows the dipole interaction term a and physical properties of the Hansen solubility parameters of the surface-treated magnetic body A6 obtained.
[0434] [Table 7]
[0435]
[0436] <Manufacturing of Toner Particles 1>
[0437] A total of 450 parts of a 0.1 mol / L-Na3PO4 aqueous solution was added to 720 parts of ion exchange water, followed by heating to a temperature of 60°C, and then 67.7 parts of a 1.0 mol / L-CaCl2 aqueous solution was added to obtain an aqueous medium including a dispersion stabilizer.
[0438]
[0439] (manufactured by Hodogaya Chemical Co., Ltd.)
[0440] - 65.0 parts of surface treated magnetic body A1
[0441] The above materials were uniformly dispersed and mixed using an attritor (Nippon Coke Industry Co., Ltd.) The monomer composition was heated to a temperature of 60° C., and the following materials were mixed and dissolved therein to obtain a polymerizable monomer composition.
[0442] - Crystalline material D1 10.0 parts
[0443] - Crystalline material E1 3.0 parts
[0444] (HNP-51: manufactured by Nippon Seiro Co., Ltd.)
[0445] - 10.0 parts of polymerization initiator
[0446] (tert-Butyl peroxypivalate (25% toluene solution))
[0447] The polymerizable monomer composition was put into an aqueous medium and granulated by stirring at 10,000 rpm with a TK homomixer (Tokushu Kika Kogyo Co., Ltd.) in a N2 atmosphere at 60° C. Thereafter, the mixture was stirred with a paddle stirring blade and a polymerization reaction was performed at a reaction temperature of 70° C. for 300 minutes.
[0448] After the reaction was completed, the temperature was raised to 98°C and distilled for 3 hours to obtain a reaction slurry. Thereafter, as a cooling step, 0°C water was added to the suspension, and the suspension was cooled from 100°C to 30°C at a rate of 100°C / min, and then heated to 50°C and maintained for 6 hours.
[0449] The suspension was then naturally cooled to 25° C. at room temperature. The cooling rate at this time was 1° C. / min. Thereafter, hydrochloric acid was added to the suspension for sufficient washing, thereby dissolving the dispersion stabilizer, followed by filtration and drying to obtain toner particles 1. Table 8 shows the formulation of the obtained toner particles 1.
[0450] [Table 8]
[0451]
[0452] <Manufacturing of Toner Particles 2 to 21>
[0453] Toner particles 2 to 21 were obtained by performing the same operation as in the production of toner particle 1, except that the kind and amount of the surface-treated magnetic body A, the kind and amount of monomers constituting resin B, resin C, crystalline material D, and crystalline material E, and the cooling rate in the cooling step were changed as shown in Table 8 in the production of toner particle 1. The physical properties of the produced toner particles are shown in the above Table 8.
[0454] <Production Example of Toner 1>
[0455] A total of 0.3 parts of sol-gel silica fine particles having a primary particle number average particle diameter of 115 nm were added to 100 parts of toner particles 1 and mixed using an FM mixer (manufactured by Nippon Coke Industries, Ltd.). Thereafter, 0.9 parts of silica fine particles having a primary particle number average particle diameter of 12 nm obtained by treating hexamethyldisilazane and then treating with silicone oil and having a BET specific surface area value of 120 m 2 / g of hydrophobic silica fine particles, followed by mixing with an FM mixer (manufactured by Nippon Coke Industries, Ltd.) as well, to obtain Toner 1.
[0456] The results of Toner 1 obtained are shown in Table 9 below.
[0457] [Table 9]
[0458]
[0459] *1: Temperature (°C) when the storage elastic modulus E' measured at the start of measurement decreases by 50%
[0460] *2: Load at yield point (mN)
[0461] <Manufacturing Examples of Toners 2 to 21>
[0462] Toners 2 to 21 were obtained in the same manner as in the Production Example of Toner 1, except that the toner particles shown in Table 9 were used in the Production Example of Toner 1. Table 9 shows the physical properties of Toners 2 to 21.
[0463] <Image Forming Apparatus>
[0464] LaserJet Pro M12 (manufactured by Hewlett-Packard Co.) of a one-component contact developing system was used after being modified to 200 mm / sec, which is faster than the original process speed. The evaluation results are shown in Table 10. The evaluation method and evaluation criteria in each evaluation are as follows.
[0465] <Evaluation of Storage Stability>
[0466] In the test of storage stability, after outputting a solid image under a high temperature and high humidity environment (32.5° C., 80% RH), each developing device was stored under a harsh environment (45.0° C., 90% RH) for 30 days. After storage, a solid image was output under a high temperature and high humidity environment (32.5° C., 80% RH), and evaluation was performed according to the following criteria by using the difference in image density before and after storage. The density of the solid image was measured with a Macbeth reflection densitometer (manufactured by Macbeth Co.).
[0467] A: Image density difference is less than 0.05
[0468] B: Image density difference is 0.05 or more and less than 0.10
[0469] C: Image density difference is 0.10 or more and less than 0.20
[0470] D: Image density difference is 0.20 or more
[0471] <Evaluation of rear end offset (low temperature fixability)>
[0472] The low-temperature fixability was evaluated under a normal temperature and high humidity environment (25.0° C., 80% RH).
[0473] As the evaluation image, the image was printed on Canon A4 size Oce Red Label paper (basic weight 80g / m 2 ) with left and right margins adjusted to 5 mm and top and bottom margins adjusted to 5 mm. As a result of setting the image on the toner not placed in the thermistor portion of the fixing device in this manner, temperature control was not performed, making the evaluation conditions more severe.
[0474] Using this image, while changing the set temperature control every 5° C. in the fixing temperature range of 170° C. to 200° C., the presence or absence of the trailing end offset at each fixing temperature was visually confirmed.
[0475] Evaluation was made based on the following criteria.
[0476] A: No rear end contamination at 170°C
[0477] B: No rear end contamination at 175°C
[0478] C: No rear end contamination at 180°C
[0479] D: Back-end contamination occurs above 185°C
[0480] <Fog on Post-White Paper in a High Temperature and High Humidity Environment>
[0481] The evaluation of fogging on white back paper was performed under a high temperature and high humidity environment (32.5° C., 80% RH). The measurement of fogging was performed using REFLECTMETER MODEL TC-6DS manufactured by Tokyo Denshoku Co., Ltd. A green filter was used as a filter.
[0482] By using the above-mentioned image forming apparatus to print 1,500 sheets and 3,000 sheets, a sheet having a Output a white image on the paper and remove Subtract the reflectivity of the paper from the The reflectivity of the white background other than the background is used to calculate the "fogging on the white paper".
[0483] A: Less than 5.0%
[0484] B: 5.0% or more and less than 10.0%
[0485] C: 10.0% or more and less than 15.0%
[0486] D: 15.0% or more
[0487] [Table 10]
[0488]
[0489] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. A toner comprising toner particles including a binder resin and a resin C, It is characterized in that The toner is such that: (1) When the powder dynamic viscoelasticity measurement method is used, the measurement start temperature is set to 25° C., and the temperature increase rate is set to 20° C. / min., on a curve of the storage elastic modulus E' in which the temperature in ° C. is plotted as the abscissa and the storage elastic modulus E' in Pa is plotted as the ordinate, the temperature at which the storage elastic modulus E' at the start of the measurement decreases by 50% is 60° C. to 90° C., (2) the load at the yield point of a displacement-load curve determined by nanoindentation method, in which the load in mN is plotted on the ordinate and the displacement in μm is plotted on the abscissa, is 0.80 mN or more, The resin C is a non-crystalline polyester resin including an isosorbide unit represented by the following formula (1), The toner particles include a surface-treated magnetic body A having a magnetic body and a hydrophobic treatment agent on the surface of the magnetic body, the hydrophobic treatment agent including an organic compound having a hydrophobic group, The organic compound having a hydrophobic group includes a silane compound having a hydrocarbon group having 8 to 16 carbon atoms, and The amount of carbon derived from the silane compound in the surface-treated magnetic body A is less than 0.5 mass %.
2. The toner according to claim 1, wherein When the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a MPa 1 / 2 When , a is 1.40 to 2.
10.
3. The toner according to claim 1 or 2, wherein The binder resin includes resin B, and When the dipole interaction term of the Hansen solubility parameter of the resin B is taken as b MPa 1 / 2 and the dipole interaction term of the Hansen solubility parameter of the resin C is taken as c MPa 1 / 2 When b <c。 4. The toner according to claim 3, wherein When the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a MPa 1 / 2 , The dipole interaction term of the Hansen solubility parameter of the resin B is taken as b MPa 1 / 2 ,and The dipole interaction term of the Hansen solubility parameter of the resin C is taken as c MPa 1 / 2 When , the following inequality (1) is satisfied: b <a<c (1)。 5. The toner according to claim 3, wherein When the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a MPa 1 / 2 , The dipole interaction term of the Hansen solubility parameter of the resin B is taken as b MPa 1 / 2 ,and The dipole interaction term of the Hansen solubility parameter of the resin C is taken as c MPa 1 / 2 When , the following inequalities (2) and (3) are satisfied: |ba|≤1.10 (2) |ca|≤4.60 (3).
6. The toner according to claim 1 or 2, wherein The toner particles include a crystalline material D, and When the dipole interaction term of the Hansen solubility parameter of the crystalline material D is taken as d MPa 1 / 2 , and the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a MPa 1 / 2 When , the following inequality (4) is satisfied: |da|≤0.75 (4).
7. The toner according to claim 1 or 2, wherein The toner particles include a crystalline material E The amount of the crystalline material E is 5.0 parts by mass or less relative to 100.0 parts by mass of the binder resin, and When the dipole interaction term of the Hansen solubility parameter of the crystalline material E is taken as e MPa 1 / 2 , and the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a MPa 1 / 2 When , the following inequality (5) is satisfied: |ea|≥1.50 (5).
8. The toner according to claim 6, wherein The toner particles include a crystalline material D, and In a cross section of the toner observed with a transmission electron microscope, When the number of toners having domains of the crystalline material D having a major diameter of 500 nm or more is taken as B1, and the number of toners not having domains of the crystalline material D having a major diameter of 500 nm or more is taken as C1, the following inequality (6) is satisfied: B1 / (B1+C1)≤0.20 (6).
9. The toner according to claim 1 or 2, wherein In a cross section of the toner observed with a transmission electron microscope, When the area ratio of the surface-treated magnetic body A within a range of 200 nm or less from the cross-sectional contour of the toner particle toward the center of gravity of the toner particle in the cross section is taken as A1, the area ratio A1 is 35% to 80%.
10. A method for producing a toner, the toner comprising toner particles including a binder resin and a resin C, It is characterized in that The method comprises: Step (I): dispersing a polymerizable monomer composition including a polymerizable monomer capable of forming the binder resin in an aqueous medium, and forming particles of the polymerizable monomer composition in the aqueous medium, and Step (II): polymerizing the polymerizable monomer included in the particles of the polymerizable monomer composition, wherein The toner is such that (1) When the powder dynamic viscoelasticity measurement method is used, the measurement start temperature is set to 25° C., and the temperature increase rate is set to 20° C. / min, on a curve of the storage elastic modulus E' in which the temperature in ° C. is plotted as the abscissa and the storage elastic modulus E' in Pa is plotted as the ordinate, the temperature at which the storage elastic modulus E' at the start of the measurement decreases by 50% is 60° C. to 90° C., and (2) the load at the yield point of a displacement-load curve determined by nanoindentation method, in which the load in mN is plotted on the ordinate and the displacement in μm is plotted on the abscissa, is 0.80 mN or more, and The polymerizable monomer composition comprises a surface-treated magnetic body A and the resin C, The resin C is a non-crystalline polyester resin including an isosorbide unit represented by the following formula (1), The toner particles include a surface-treated magnetic body A having a magnetic body and a hydrophobic treatment agent on the surface of the magnetic body, the hydrophobic treatment agent including an organic compound having a hydrophobic group, The organic compound having a hydrophobic group includes a silane compound having a hydrocarbon group having 8 to 16 carbon atoms, and The amount of carbon derived from the silane compound in the surface-treated magnetic body A is less than 0.5 mass %.
11. The method for producing a toner according to claim 10, wherein When the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a MPa 1 / 2 When , a is 1.40 to 2.
10.
12. The method for producing a toner according to claim 10 or 11, wherein The polymerizable monomers include a polymerizable monomer b capable of forming a resin B, and When the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a MPa 1 / 2 , The dipole interaction term of the Hansen solubility parameter of the resin B is taken as b MPa 1 / 2 ,and The dipole interaction term of the Hansen solubility parameter of the resin C is taken as c MPa 1 / 2 When , the following inequality (1) is satisfied: b <a<c (1)。 13. The method for producing a toner according to claim 12, wherein When the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a MPa 1 / 2 , The dipole interaction term of the Hansen solubility parameter of the resin B is taken as b MPa 1 / 2 ,and The dipole interaction term of the Hansen solubility parameter of the resin C is taken as c MPa 1 / 2 When , the following inequalities (2) and (3) are satisfied: |ba|≤1.10 (2) |ca|≤4.60 (3).
14. The method for producing a toner according to claim 10 or 11, wherein The polymerizable monomer composition includes a crystalline material D, and When the dipole interaction term of the Hansen solubility parameter of the crystalline material D is taken as d MPa 1 / 2 , and the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a MPa 1 / 2 When , the following inequality (4) is satisfied: |da|≤0.75 (4).
15. The method for producing a toner according to claim 10 or 11, wherein The polymerizable monomer composition includes a crystalline material E, The amount of the crystalline material E is 5.0 parts by mass or less relative to 100.0 parts by mass of the polymerizable monomer capable of forming the binder resin, and When the dipole interaction term of the Hansen solubility parameter of the crystalline material E is taken as e MPa 1 / 2 , and the dipole interaction term of the Hansen solubility parameter of the surface-treated magnetic body A is taken as a MPa 1 / 2 When , the following inequality (5) is satisfied: |ea|≥1.50 (5).
